1-butene-propylene-ethylene copolymer, polymer composition, molded body, laminate, and power storage device
Patent Information
- Application Number
- CN202580022930.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-03-29
- Filing Date
- 2025-03-27
- Publication Date
- 2026-10-27
AI Technical Summary
本公开文本可以提供柔软性和拉伸强度优异的1-丁烯·丙烯·乙烯共聚物、包含该共聚物的聚合物组合物、成型体、包含该成型体的层叠体及包含该成型体的蓄电装置。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This disclosure relates to 1-butene-propylene-ethylene copolymers, polymer compositions, molded articles, laminates, and energy storage devices. Background Technology
[0002] 1-Butene polymers exhibit excellent creep properties, wear resistance, flexibility, and compatibility with polypropylene at high temperatures, making them suitable for the modification of water supply and hot water pipes, sheet materials such as skin materials, polypropylene resins, and hot melt adhesives.
[0003] In Patent Document 1, a resin modifier and a hot melt adhesive containing the 1-butene polymer are known as 1-butene polymers with good balance of flowability, tensile modulus of elasticity and elongation and secondary processability. The 1-butene polymer has an intrinsic viscosity [η] of 0.01 to 0.5 dl / g measured at 135°C in tetrahydronaphthalene solvent, a melting point of 0 to 100°C measured by differential scanning calorimetry (DSC), and a stereoregularity index {(mmmm) / (mmrr+rmmr)} of 30 or less.
[0004] In addition, in Patent Document 2, there is a known 1-butene (co)polymer with a content of 25 to 55 mol% of structural units derived from 1-butene, having an isotactic five-unit group (mmmm) morphology, and having a balance with the elastomeric properties (fracture tensile stress or yield point tensile stress) that contribute to compressive permanent strain, elongation at break and crystallinity.
[0005] Existing technical documents Patent documents Patent Document 1: International Publication No. 03 / 070788 Patent Document 2: Japanese Patent Publication No. 2008-517130 Summary of the Invention
[0006] The problem that the invention aims to solve However, 1-butene polymers with reduced stereoregularity and low isotactic five-unit component ratios (mmmm), or 1-butene copolymers obtained by copolymerizing 1-butene with α-olefins, exhibit a problem where tensile strength decreases with increasing flexibility.
[0007] The purpose of this disclosure is to provide a 1-butene-propylene-ethylene copolymer with excellent flexibility and tensile strength, and a polymer composition comprising the copolymer. Furthermore, the purpose of this disclosure is to provide a molded article with excellent balance between flexibility and tensile strength, a laminate comprising the molded article, and an energy storage device comprising the molded article.
[0008] Methods for solving problems The inventors of this application conducted in-depth research to solve the aforementioned problems and discovered that the problems could be solved by following examples, thereby completing the present invention. Examples of the present invention are shown below.
[0009] [1] 1-Butene-propylene-ethylene copolymer (A), which satisfies the following requirements (A1) and (A2): (A1) The content of the structural unit (i) derived from 1-butene is 50~96 mol%. The content of propylene-derived structural unit (ii) is 1-40 mol%. And, the content of the ethylene-derived structural unit (iii) is 3 to 20 mol% (wherein, the total of the structural unit (i), the structural unit (ii) and the structural unit (iii) is set to 100 mol%). (A2) The ratio of weight-average molecular weight (Mw) to number-average molecular weight (Mn) (Mw / Mn) determined by gel permeation chromatography (GPC) and converted to polystyrene is less than 3.0.
[0010] [2] The 1-butene-propylene-ethylene copolymer (A) as described in item [1] satisfies at least one of the following requirements (A3) and (A4): (A3) The melt flow rate (MFR) measured according to ASTM D1238 at 230°C and 2.16 kg load is 1~100 g / 10 min; (A4) The molar ratio (1-butene / ethylene) of the content of structural unit (i) derived from 1-butene to the content of structural unit (iii) derived from ethylene is 6 or more.
[0011] [3] The 1-butene-propylene-ethylene copolymer (A) as described in item [1] or [2], wherein the molar ratio (1-butene / ethylene) of the aforementioned element (A4) is 9.1 or more.
[0012] [4] The 1-butene-propylene-ethylene copolymer (A) as described in any of [1] to [3] satisfies the following requirement (A8): (A8) The melting point (Tm) measured during the first heating of the differential scanning calorimeter (DSC) was observed below 60°C, and the measured enthalpy of fusion was 2~50 J / g. No melting peak was observed during the second heating.
[0013] [5] The 1-butene-propylene-ethylene copolymer (A) as described in any one of items [1] to [4] satisfies the following requirement (A5): (A5) Through 13The isotactic five-unit composition (mmmm) calculated by C-NMR is over 90%.
[0014] [6] A polymer composition (X) comprising: The 1-butene-propylene-ethylene copolymer (A) mentioned in any one of items [1] to [5], and A propylene polymer (B) that meets the following requirements (B1) and (B2).
[0015] (B1) The melting point (Tm) measured during the first heating of the differential scanning calorimeter (DSC) is 100~170℃.
[0016] (B2) Through 13 The isotactic five-unit composition (mmmm) calculated by C-NMR is over 80%.
[0017] [7] The polymer composition (X) as described in item [6], wherein the aforementioned propylene polymer (B) is atactic polypropylene or block polypropylene.
[0018] [8] The polymer composition (X) as described in item [6] or [7] satisfies the following requirements (X1-2): The content of (X1-2) 1-butene-propylene-ethylene copolymer (A) is 1~36% by mass, and the content of propylene polymer (B) is 64~99% by mass (wherein, the total of copolymer (A) and propylene polymer (B) is set to 100% by mass).
[0019] [9] The polymer composition (X) as described in item [6] or [7] further comprises an ethylene polymer (C).
[0020]
[10] The polymer composition (X) as described in item [9], wherein the aforementioned propylene polymer (B) is atactic polypropylene or block polypropylene.
[0021]
[11] The polymer composition (X) as described in item [9] or
[10] , wherein the aforementioned ethylene polymer (C) is a high-pressure low-density polyethylene satisfying the following requirement (C1) or an ethylene-α-olefin copolymer satisfying the following requirement (C2): (C1) The density of high-pressure low-density polyethylene, measured according to ASTM D1505, is 900~925 kg / m³. 3 , (C2) Through 13The ethylene-α-olefin copolymer, as determined by C-NMR, has at least ethylene-derived structural units and α-olefin-derived structural units with 3 to 20 carbon atoms, wherein the content of the ethylene-derived structural units is 60 to 99 mol%, and the content of the α-olefin-derived structural units with 3 to 20 carbon atoms is 1 to 40 mol%.
[0022]
[12] The polymer composition (X) as described in any one of items [9] to
[11] satisfies the following requirements (X1-3): (X1-3) The content of 1-butene-propylene-ethylene copolymer (A) is 8-35% by mass, the content of propylene polymer (B) is 48-88% by mass, and the content of ethylene polymer (C) is 4-17% by mass (wherein, the total content of the copolymer (A), the polymer (B) and the polymer (C) is set as 100% by mass).
[0023]
[13] The polymer composition (X) as described in item [6] or [7] satisfies the following requirement (X1-1): (X1-1) The content of 1-butene-propylene-ethylene copolymer (A) is higher than 36% by mass and lower than 99% by mass, and the content of propylene polymer (B) is higher than 1% by mass and lower than 64% by mass (wherein, the total of 1-butene-propylene-ethylene copolymer (A) and propylene polymer (B) is set to 100% by mass).
[0024]
[14] A molded body, comprising: The 1-butene-propylene-ethylene copolymer (A) mentioned in any one of items [1] to [5], or The polymer composition (X) described in any one of items [6] to
[13] .
[0025]
[15] The molded body as described in item
[14] is a film.
[0026]
[16] A laminate, comprising the molded body described in item
[14] .
[0027]
[17] An energy storage device comprising the molded body described in item
[14] .
[0028] Invention Effects This disclosure provides a 1-butene-propylene-ethylene copolymer with excellent flexibility and tensile strength, a polymer composition comprising the copolymer, a molded article, a laminate comprising the molded article, and an energy storage device comprising the molded article. Detailed Implementation
[0029] In this specification, the numerical range represented by "~" refers to the range including the values before and after "~" as the lower and upper limits. "A~B" indicating a numerical range means above A and below B.
[0030] In this manual, when the units of the values before and after the "~" indicating a numerical range are the same, the unit of the value before the "~" is sometimes omitted. For example, sometimes "851 kg / m 3 ~900kg / m 3 The record states "851~900 kg / m³". 3 ".
[0031] In this specification, when referring to the amount of each component in the composition, if multiple substances belonging to each component are present in the composition, unless otherwise specified, the total amount of the multiple substances present in the composition is used.
[0032] In this specification, a combination of two or more preferred methods is a more preferred method.
[0033] Unless otherwise specified, each component in the composition or each structural unit in the polymer (resin) may contain one or more types of components in this specification.
[0034] In this instruction manual, "room temperature" and "normal temperature" refer to 23°C.
[0035] [1-Butene·propylene·ethylene copolymer (A)] The 1-butene-propylene-ethylene copolymer (A) of this disclosure (hereinafter also referred to as "copolymer (A)") satisfies the following requirements (A1) and (A2).
[0036] (A1) The content of structural unit (i) derived from 1-butene is 50 to 96 mol%, the content of structural unit (ii) derived from propylene is 1 to 40 mol%, and the content of structural unit (iii) derived from ethylene is 3 to 20 mol% (wherein the total content of structural unit (i), structural unit (ii) and structural unit (iii) is set to 100 mol%).
[0037] The minimum content of the 1-butene-derived structural unit (i) in copolymer (A) is 50 mol%. The minimum content of structural unit (i) is preferably 55 mol%, more preferably 57.5 mol%, further preferably 71 mol%, and particularly preferably 72 mol%.
[0038] On the other hand, the upper limit of the content of the structural unit (i) derived from 1-butene is 96 mol%, preferably 93 mol%, more preferably 87.8 mol%.
[0039] That is, the content of the above-mentioned structural unit (i) is preferably 55 to 93 mol%, more preferably 57.5 to 87.8 mol%, even more preferably 71 to 87.8 mol%, and particularly preferably 72 to 87.8 mol%.
[0040] If the content of the structural unit (i) derived from 1-butene is within the above range, it has excellent flexibility and compatibility with propylene polymers (B), and is therefore preferred.
[0041] The minimum content of the propylene-derived structural unit (ii) in copolymer (A) is 1 mol%. The minimum content of structural unit (ii) is preferably 3 mol%, more preferably 7.2 mol%.
[0042] On the other hand, the upper limit of the content of the propylene-derived structural unit (ii) is 40 mol%, preferably 38 mol%, and more preferably 36 mol%.
[0043] That is, the content of the above-mentioned structural unit (ii) is preferably 3 to 38 mol%, more preferably 7.2 to 36 mol%.
[0044] If the content of the propylene-derived structural unit (ii) is within the above range, it is preferred because it has excellent flexibility, tensile strength and compatibility with propylene-based polymers (B).
[0045] The minimum content of the ethylene-derived structural unit (iii) in the copolymer (A) is 3 mol%, preferably 4 mol%, and more preferably 5 mol%.
[0046] On the other hand, the upper limit of the content of the ethylene-derived structural unit (iii) is 20 mol%, preferably 13 mol%, more preferably 10.1 mol%, and even more preferably 9.5 mol%.
[0047] That is, the content of the above-mentioned structural unit (iii) is preferably 4 to 13 mol%, more preferably 5 to 10.1 mol%, and even more preferably 5 to 9.5 mol%.
[0048] If the content of the ethylene-derived structural unit (iii) is within the above range, it is preferred because it has excellent flexibility and compatibility with propylene polymers (B).
[0049] The copolymer (A) may also have other structural units besides structural units (i), (ii), and (iii). Examples of polymerizable monomers from which other structural units are derived include, for example, 4-methyl-1-pentene, 1-hexene, 1-octene, vinyl compounds, vinyl esters, conjugated dienes, and non-conjugated polyenes.
[0050] Based on the mass of copolymer (A), the total content of structural unit (i), structural unit (ii) and structural unit (iii) in copolymer (A) is preferably 80% by mass or more, more preferably 85% by mass or more, further preferably 90% by mass or more, even more preferably 95% by mass or more, and particularly preferably 98% by mass or more.
[0051] The copolymer (A) may have at least one structural unit derived from a monomer derived from biomass. Examples of monomers derived from biomass include 1-butene, propylene, and ethylene. The same type of monomers constituting the copolymer may be derived solely from biomass, solely from fossil fuels, or may include both monomers derived from biomass and monomers derived from fossil fuels.
[0052] For copolymer (A), good compatibility with the propylene polymer (B) described later can be obtained by keeping the content of the ethylene-derived structural unit (iii) within the above-mentioned range. If the content of the ethylene-derived structural unit (iii) is below the upper limit, the mechanical strength is excellent, for example, when used as a hot melt adhesive, the adhesive strength is excellent, which is preferred from this perspective. When used as a packaging material, the durability of the film is improved, which is also preferred. In addition, if it is above the lower limit, the crystallization rate becomes appropriate. For example, when used as a modifier for nonwoven fabrics, the molding conditions for stable spinning are widened, and the formability is improved, which is also preferred. When used as a hot melt adhesive, the long open time, a feature of this disclosure, can be fully utilized, which is also preferred. When used as a packaging material, when combined with the propylene polymer, the flexibility and impact resistance are excellent, which is also preferred.
[0053] The content (mol%) of each structural unit constituting copolymer (A) is determined by... 13 The determination is performed using C-NMR. It should be noted that details regarding the determination method are described in the Examples section below.
[0054] (A2) The ratio of weight-average molecular weight (Mw) to number-average molecular weight (Mn) (Mw / Mn) determined by gel permeation chromatography (GPC) and converted to polystyrene is less than 3.0.
[0055] The Mw / Mn ratio of copolymer (A) is preferably 1.5 to 3.0, more preferably 1.6 to 2.6. Copolymer (A) with Mw / Mn in the above range has fewer low molecular weight components that reduce mechanical strength and fewer high molecular weight components that worsen flowability, and is therefore preferred.
[0056] The copolymer (A) preferably satisfies at least one of the following requirements (A3) and (A4) in addition to the above-mentioned requirements (A1) and (A2).
[0057] (A3) The melt flow rate (MFR) measured according to ASTM D1238 at 230°C and a load of 2.16 kg is preferably 1 to 100 g / 10 min, more preferably 2 to 90 g / 10 min, even more preferably 3 to 85 g / 10 min, and particularly preferably 3.2 to 80 g / 10 min. If the MFR is within the above range, the flowability is good, and the resulting molded article has good mechanical properties. For example, adhesives such as hot melt adhesives containing copolymer (A) have good operability and are suitable for high-speed coating. When used as a hot melt adhesive, high flowability is required; therefore, an MFR of 18 to 80 g / 10 min is particularly preferred. Furthermore, molded articles with excellent mechanical properties can be easily obtained. When used for molded articles such as packaging materials, considering the balance between flowability and mechanical properties suitable for molding machines, an MFR of 15 g / 10 min or less is preferred, and more preferably 3.2 to 15 g / 10 min.
[0058] If the MFR is above the lower limit, the copolymer (A) has good flowability, and adhesives such as hot melt adhesives containing copolymer (A) have good workability and are suitable for high-speed coating. If the MFR is below the upper limit, the copolymer (A) has excellent mechanical properties, and adhesives containing copolymer (A) are preferred from the viewpoints of adhesive strength, oil resistance, and creep resistance. When used as packaging materials, they have excellent durability and are therefore preferred.
[0059] (A4) The molar ratio (1-butene / ethylene) of the content of structural unit (i) derived from 1-butene to the content of structural unit (iii) derived from ethylene is 6 or more.
[0060] The 1-butene / ethylene ratio of copolymer (A) is preferably 8.2 or more, more preferably 9.1 or more, and even more preferably 10 or more. There is no particular upper limit to the 1-butene / ethylene ratio, but it is preferably 25 or less, more preferably 20 or less, and even more preferably 18 or less. That is, the 1-butene / ethylene ratio is preferably 8.2 to 25, more preferably 9.1 to 20, and even more preferably 10 to 18. If the 1-butene / ethylene ratio is within the above range, it exhibits excellent compatibility with the propylene-based polymer (B), and is therefore preferred. Furthermore, the slow crystallization rate results in excellent open time when used as a hot-melt adhesive.
[0061] The copolymer (A) preferably satisfies at least one of the following requirements (A5) to (A8) in addition to the above-mentioned requirements (A1) and (A2).
[0062] (A5) Through13 The isotactic five-unit composition (mmmm) calculated by C-NMR is over 90%.
[0063] The lower limit of the isotactic five-unit component ratio (mmmm) of copolymer (A) is more preferably 90.5%. Furthermore, the upper limit of the isotactic five-unit component ratio (mmmm) is not particularly limited; as an option, 99.9% is preferred, more preferably 99.5%, further preferably 99.0%, and particularly preferably 98.0%. That is, the isotactic five-unit component ratio (mmmm) is preferably 90-99.9%, more preferably 90-99.5%, further preferably 90-99.0%, and particularly preferably 90.5-98.0%. If the isotactic five-unit component ratio (mmmm) is within the above range, even when controlling compatibility with the propylene polymer (B) described later by copolymerizing ethylene, appropriate mechanical strength and flexibility can be achieved.
[0064] It should be noted that the details of the method for determining the isotactic five-unit component ratio (mmmm) are as described in the examples described later.
[0065] (A6) The intrinsic viscosity [η] in decahydronaphthalene solvent at 135℃ is 0.7~2.5 dl / g.
[0066] The intrinsic viscosity [η] of copolymer (A) is preferably 0.8 to 2.4 dl / g, more preferably 0.9 to 2.35 dl / g, even more preferably 1.0 to 2.3 dl / g, and particularly preferably 1.0 to 1.9 dl / g. Copolymer (A) with intrinsic viscosity [η] in the above range exhibits excellent balance between flowability and mechanical strength.
[0067] For example, adhesives containing copolymer (A) such as hot melt adhesives have good workability and are suitable for high-speed coating. In addition, molded articles with excellent mechanical properties can be easily obtained, and both ease of molding and durability of packaging materials can be achieved simultaneously, making them preferred.
[0068] (A7) Weight average molecular weight (Mw) is 100,000~400,000.
[0069] When fluidity is required, the weight-average molecular weight is preferably 100,000 to 400,000, more preferably 100,000 to 390,000, and particularly preferably 100,000 to 380,000. If the weight-average molecular weight is within the above range, the adhesive, such as a hot melt adhesive containing copolymer (A), exhibits good workability and is suitable for high-speed coating. Furthermore, when mechanical strength is required, the weight-average molecular weight (Mw) is preferably 110,000 to 380,000, more preferably 120,000 to 380,000, further preferably 132,000 to 380,000, and particularly preferably 180,000 to 380,000. If the weight-average molecular weight is within the above range, molded articles with excellent mechanical properties can be easily obtained. Additionally, when used as a hot melt adhesive, the adhesive strength is improved.
[0070] (A8) The melting point (Tm) measured during the first heating of the differential scanning calorimeter (DSC) was observed below 60°C, and the measured enthalpy of fusion was 2~50 J / g. In the heat measurement using the differential scanning calorimeter (DSC), no melting peak was observed during the second heating.
[0071] In the determination of the calorimetry of copolymer (A) using differential scanning calorimetry (DSC), approximately 6-10 mg of sample was accurately weighed, sealed in an aluminum dish, and cooled from room temperature to -70°C at a cooling rate of 20°C / min (first cooling). The sample was then held at -70°C for 5 minutes, and heated from -70°C to 200°C at a heating rate of 20°C / min (first heating). The result was measured using DSC. The sample was held at 200°C for 10 minutes, then cooled to -70°C at a cooling rate of 20°C / min (second cooling). The result was measured using DSC. The sample was held at -70°C for 1 minute, and then heated again from -70°C to 200°C at a heating rate of 20°C / min (second heating). The result was measured using DSC.
[0072] In this specification, the melting peak is determined using the method described above. The melting point refers to the temperature at the apex of the melting peak. "Unobservable melting peak" means that no crystalline melting peak with a melting enthalpy greater than 1 J / g is observed. It should be noted that if two or more melting peaks are observed, the lowest temperature among the apex temperatures of these peaks is the melting point.
[0073] For copolymer (A), the melting point (Tm) measured during the first heating of the differential scanning calorimeter (DSC) is preferably below 55°C.
[0074] For copolymer (A), when the melting point is observed during the first heating of a differential scanning calorimeter (DSC), the measured enthalpy of fusion is preferably 2 to 50 J / g, more preferably 15 to 40 J / g. The enthalpy of fusion serves as an indicator of crystallinity. If the enthalpy of fusion is below the upper limit, the crystallinity is low, resulting in excellent softness and improved flexibility and deformation following properties as a hot melt adhesive. If the enthalpy of fusion is above the lower limit, the mechanical properties are excellent, resulting in improved adhesive strength as a hot melt adhesive. If the enthalpy of fusion is within the above range, the balance between softness and low tackiness is excellent.
[0075] The fact that a melting peak was observed during the first heating, and that no melting peak was observed during the second heating even though the copolymer (A) exhibits crystallinity, indicates that the crystallization rate of the copolymer (A) is extremely slow. Therefore, when copolymer (A) is used as a modifier for nonwoven fabrics, the molding conditions for stable spinning of the nonwoven fabric are broadened, and the moldability is improved, making it preferred. Furthermore, when used as an adhesive, it exhibits excellent adhesive strength after curing and can increase the open time during coating.
[0076] In one embodiment of the copolymer (A), when the total content of structural unit (i), structural unit (ii) and structural unit (iii) is set to 100 mol%, the content of structural unit (i) is 50 to 96 mol%, the content of structural unit (ii) is 1 to 40 mol%, the content of structural unit (iii) is 3 to 20 mol%, the ratio of the weight-average molecular weight (Mw) to the number-average molecular weight (Mn) (Mw / Mn) is 3.0 or less, the melt flow rate (MFR) is 1 to 100 g / 10 min, and the molar ratio of the content of structural unit (i) to the content of structural unit (iii) (1-butene / ethylene) is 6 or more.
[0077] In one embodiment of the copolymer (A), when the total content of structural units (i), (ii), and (iii) is set to 100 mol%, the content of structural unit (i) is 50-96 mol%, the content of structural unit (ii) is 1-40 mol%, the content of structural unit (iii) is 3-20 mol%, the weight-average molecular weight (Mw) to number-average molecular weight (Mn) ratio (Mw / Mn) is 3.0 or less, the melt flow rate (MFR) is 1-100 g / 10 min, the molar ratio of the content of structural unit (i) to the content of structural unit (iii) (1-butene / ethylene) is 9.1 or more, the melting point (Tm) measured during the first heating of the differential scanning calorimeter (DSC) is observed to be below 60°C, the measured enthalpy of fusion is 2-50 J / g, and no melting peak is observed during the second heating. 13 The isotactic five-unit composition (mmmm) calculated by C-NMR is over 90%.
[0078] For copolymer (A), it is preferred that the Shore A hardness (according to ASTM D2240, instantaneous value) is 5 to 99 or the Shore D hardness (according to ASTM D2240, maximum value) is 70 or less. A more preferred range for Shore A hardness is 75 to 98. A more preferred range for Shore D hardness is 20 to 68, a further preferred range is 25 to 65, and a particularly preferred range is 25 to 40. Shore A hardness or Shore D hardness serves as an indicator of crystallinity. If the Shore A hardness or Shore D hardness is below the upper limit, the crystallinity is low, and molded articles with excellent flexibility can be easily obtained. Furthermore, when used as a hot melt adhesive, flexibility and deformation following are improved. If the Shore A hardness or Shore D hardness is above the lower limit, molded articles with excellent mechanical properties can be easily obtained. Furthermore, when used as a hot melt adhesive, the bond strength is improved.
[0079] <Method for manufacturing 1-butene-propylene-ethylene copolymer (A)> As a method for obtaining copolymer (A), examples include polymerization of monomers using known polymerization methods such as gas-phase polymerization, bulk polymerization, and slurry polymerization in the presence of catalysts such as Ziegler-Natta catalysts and metallocene catalysts. Among these methods, considering that the polymer has a narrow molecular weight and composition distribution, can be molded into a molded body with excellent balance between mechanical strength and flexibility, and can obtain good compatibility, especially when combined with the propylene polymer (B) described later, and can delay the crystallization rate in hot melt adhesives, it is preferable to use a metallocene catalyst that can uniformly control the reaction, and it is particularly preferable to use a metallocene compound represented by the following general formula (1) or (2) for polymerization.
[0080] [Chemical Formula 1] [Chemical Formula 2] R in the above general formula (1) or (2) 1 R 2 R 3 R 4 R 5 R 6 R 7 R 8 R 9 R 10 R 11 R 12The elements are selected from hydrogen, hydrocarbon groups, and silicon-containing hydrocarbon groups, and these groups can be the same or different. M is a metal selected from Group 4 of the periodic table. j is an integer from 1 to 4. Q can be selected from halogens, hydrocarbon groups with 1 to 20 carbon atoms, anionic ligands, or neutral ligands that can coordinate with lone pairs of electrons, in the same or different combinations.
[0081] In the case of general formula (2), Y is bonded to a divalent hydrocarbon group A with 2 to 20 carbon atoms that may contain unsaturated bonds and / or aromatic rings, to form a cycloalkyl group or a cyclomethylene silyl group, etc.
[0082] The preferred hydrocarbon group is an alkyl group with 1 to 20 carbon atoms, an arylalkyl group with 7 to 20 carbon atoms, an aryl group with 6 to 20 carbon atoms, or an alkylaryl group with 7 to 20 carbon atoms. It may also contain one or more ring structures. Specific examples include methyl, ethyl, n-propyl, isopropyl, 2-methylpropyl, 1,1-dimethylpropyl, 2,2-dimethylpropyl, 1,1-diethylpropyl, 1-ethyl-1-methylpropyl, 1,1,2,2-tetramethylpropyl, sec-butyl, tert-butyl, etc.
[0083] As a silicon-containing hydrocarbon group, it is preferably an alkylsilyl or arylsilyl group with 1 to 4 silicon atoms and 3 to 20 carbon atoms. Specific examples include trimethylsilyl, tert-butyldimethylsilyl, and triphenylsilyl.
[0084] It should be noted that R 2 Preferably, the substituent is a hydrocarbon group with a large stereochemical volume, a silicon-containing hydrocarbon group, i.e., a secondary or tertiary substituent, and more preferably a substituent with 4 or more carbon atoms. Specific examples of hydrocarbon groups include isopropyl, 1,1-dimethylpropyl, 1,1-diethylpropyl, 1-ethyl-1-methylpropyl, 1,1,2,2-tetramethylpropyl, sec-butyl, tert-butyl, and 1,1-dimethylbutyl. Tert-butyl is particularly preferred. Silicon-containing hydrocarbon groups can be exemplified by compounds in which some or all of the carbon atoms are replaced by silicon.
[0085] R on the fluorene ring 5 To R 12 Adjacent substituents can bond with each other to form a ring. Examples of such substituted fluorene groups include benzo[a]fluorene and dibenzo[a]fluorene. Additionally, the R group on the fluorene ring... 5 To R 12 From a synthetic ease perspective, the substituents are preferably left-right symmetrical, i.e., R 5 =R 12 R 6 =R 11 R 7 =R 10 R 8 =R 9More preferably, it is an unsubstituted fluorene, a 3,6-disubstituted fluorene, a 2,7-disubstituted fluorene, or a 2,3,6,7-tetrasubstituted fluorene. Here, positions 3, 6, 2, and 7 on the fluorene ring each correspond to R. 7 R 10 R 6 R 11 R in the above general formula (1) 3 and R 4 The group is selected from hydrogen and hydrocarbon groups, which may be the same or different. As a specific example of a preferred hydrocarbon group, the same hydrocarbon group as described above can be given. Y is carbon or silicon. In the case of general formula (1), R... 13 and R 14 It bonds to Y and serves as a crosslinking portion, constituting a substituted methylene or substituted methylenesilyl group. Preferred specific examples include, for instance, methylene, dimethylmethylene (isopropylene), diisopropylmethylene, methyl tert-butylmethylene, dicyclohexylmethylene, methylcyclohexylmethylene, methylphenylmethylene, diphenylmethylene or dimethylmethylenesilyl, diisopropylmethylenesilyl, etc. More preferably, Y is carbon.
[0086] R of general formula (1) or (2) 2 When it is tert-butyl, R 1 Preferably methyl or ethyl, more preferably methyl. In this case, R of general formula (1) 3 R 4 It is methyl or phenyl, preferably methyl. Additionally, R 3 R 4 Preferably, they are the same. Furthermore, R in the above general formula (1) 2 For tert-butyl, R 1 When it is methyl, R 5 ~R 12 It can be hydrogen.
[0087] Furthermore, R in the above general formula (1) 2 For tert-butyl, R 1 When the ethyl group is used, R is preferred. 5 R 7 R 8 R 9 R 10 R 12 For hydrogen, R 6 R 11 It is a tert-butyl compound.
[0088] In the case of general formula (2), Y is bonded to a divalent hydrocarbon group A with 2 to 20 carbon atoms, which may contain unsaturated bonds and / or aromatic rings, to form a cycloalkylene group or a cyclomethylene silylene group, etc. As preferred specific examples, cyclopropylene, cyclobutylene, cyclopentylene, cyclohexylene, etc. can be cited.
[0089] In general formulas (1) and (2), M is a metal selected from Group 4 of the periodic table. Examples of M include titanium, zirconium, and hafnium. Q can be selected from halogens, hydrocarbon groups with 1 to 20 carbon atoms, anionic ligands, or neutral ligands that can coordinate with lone pairs of electrons, in the same or different combinations. Specific examples of halogens are fluorine, chlorine, bromine, and iodine. Specific examples of hydrocarbon groups can be the same hydrocarbon groups mentioned above. Specific examples of anionic ligands can be alkoxy groups such as methoxy, tert-butoxy, and phenoxy, carboxylic acid groups such as acetate and benzoate, and sulfonate groups such as methanesulfonate and toluenesulfonate. Specific examples of neutral ligands that can coordinate with lone pairs of electrons can be organophosphorus compounds such as trimethylphosphine, triethylphosphine, triphenylphosphine, and diphenylmethylphosphine, or ethers such as tetrahydrofuran, diethyl ether, dioxane, and 1,2-dimethoxyethane. Among them, Q can be the same or different combinations, but preferably at least one is a halogen or alkyl group.
[0090] Metallocene compounds represented by general formula (1) or (2) may also be used together with component (E).
[0091] Component (E) consists of at least one compound selected from organoaluminum oxide (E-1), a compound that reacts with the aforementioned metallocene compound to form an ion pair (E-2), and an organoaluminum compound (E-3). The metallocene compound represented by general formula (1) or (2) may also be used together with a particulate support (D) as needed.
[0092] As a usable organoaluminum oxide compound (E-1), previously known aluminum oxides can be used directly.
[0093] Examples of compounds (E-2) that react with metallocene compounds to form ion pairs (hereinafter also referred to as "ionic compounds") include Lewis acids, ionic compounds, borane compounds, and carborane compounds described in Japanese Patent Application Publication No. 1-501950 and Japanese Patent Application Publication No. 2004-51676. In addition, heteropoly compounds and heteropoly compounds can also be cited.
[0094] Specifically, examples include triphenylboron, tris(o-tolyl)boron, tris(p-tolyl)boron, tris(3,5-dimethylphenyl)boron, trimethylboron, triisobutylboron; tris(4-fluorophenyl)boron, tris(3,5-difluorophenyl)boron, tris(4-fluoromethylphenyl)boron, tris(pentafluorophenyl)boron, and other compounds containing fluorine aryl groups, as well as compounds containing halogen aryl groups; trifluoroboron.
[0095] Organoaluminum compounds (E-3) used as polymerization catalysts for forming olefins can be exemplified by organoaluminum compounds represented by the following general formula (3).
[0096] Ra m Al(OR b )H p Q q q ···(3) (In the formula, R a and R b may be the same or different from each other, each representing a hydrocarbon group having 1 to 15 carbon atoms, preferably 1 to 4 carbon atoms, Q represents a halogen atom, m is a number satisfying 0<m≤3, n is a number satisfying 0≤n<3, p is a number satisfying 0≤p<3, q is a number satisfying 0≤q<3, and m+n+p+q=3.) Specific examples of such compounds include dialkylaluminum hydrides such as trimethylaluminum, triethylaluminum, tri-n-butylaluminum, diisopropylaluminum hydride, and diisobutylaluminum hydride, and alkylaluminum alkoxides such as isobutylaluminum methoxide and isobutylaluminum ethoxide.
[0097] As the organoaluminum compound (E-3), tri-n-alkylaluminums such as trimethylaluminum, triethylaluminum, and trioctylaluminum, and tri-branched alkylaluminums such as triisobutylaluminum are preferred, and trimethylaluminum and triisobutylaluminum are particularly preferably used.
[0098] In the present disclosure, the polymerization of 1-butene, propylene and ethylene can be carried out by any of liquid-phase polymerization methods such as solution polymerization and suspension polymerization, or gas-phase polymerization methods. In the liquid-phase polymerization method, an inert hydrocarbon solvent can be used, and specific examples thereof include aliphatic hydrocarbons such as propane, butane, pentane, hexane, heptane, octane and decane; alicyclic hydrocarbons such as cyclopentane, cyclohexane and methylcyclopentane; aromatic hydrocarbons such as benzene, toluene and xylene, or mixtures thereof. In addition, bulk polymerization using the olefins containing 1-butene themselves as a solvent can also be carried out.
[0099] During the polymerization, the metallocene compound is used in an amount of usually 1×10, calculated in terms of the Group 4 metal atom of the Periodic Table of the Elements, per 1 liter of the reaction volume -8 ~1×10 -2 mol, preferably 1×10 -7 ~1×10 -3 mol. Component (E-1) is used in such an amount that the molar ratio [(E-1) / M] of component (E-1) to the transition metal atom (M) in the metallocene compound is usually 0.01 to 5000, preferably 0.05 to 2000. Component (E-2) is used in such an amount that the molar ratio [(E-2) / M] of component (E-2) to the transition metal atom (M) in the metallocene compound is usually 1 to 10, preferably 1 to 5. Component (E-3) is used in such an amount that the molar ratio [(E-3) / M] of component (E-3) to the transition metal atom (M) in the metallocene compound is usually 10 to 5000, preferably 20 to 2000.
[0100] The polymerization temperature is typically -50 to 200°C, preferably 0 to 100°C, and more preferably 20 to 100°C. If the polymerization temperature is too low, it tends to be unfavorable for industrial applications in terms of polymerization activity per unit of catalyst and heat recovery efficiency.
[0101] The polymerization pressure is typically atmospheric pressure to 10 MPa gauge pressure, preferably atmospheric pressure to 5 MPa gauge pressure. The polymerization reaction can be carried out in any of the batch, semi-continuous, or continuous methods. Furthermore, the polymerization can be divided into two or more steps with different reaction conditions.
[0102] To control the molecular weight and polymerization activity of the copolymer (A) generated during polymerization, hydrogen can be added, and the appropriate amount is about 0.001 to 100 NL per 1 kg of copolymer (A).
[0103] [Polymer Composition (X)] The polymer composition (X) comprises copolymer (A). The polymer composition (X) is a composition comprising copolymer (A) and propylene polymer (B), a composition comprising copolymer (A) and ethylene polymer (C), or a composition comprising copolymer (A), propylene polymer (B), and ethylene polymer (C).
[0104] <Propylene Polymers (B)> The polymer composition (X) may contain an propylene polymer (B).
[0105] The propylene polymer (B) is a polymer other than the copolymer (A), preferably satisfying one or more of the following requirements (B1) to (B3), more preferably satisfying requirements (B1) and (B2), and even more preferably satisfying all of the requirements (B1) to (B3).
[0106] (B1) The melting point (Tm) measured during the first heating of the differential scanning calorimeter (DSC) is 100~170℃, preferably 130~170℃.
[0107] The melting point (Tm) of the propylene polymer (B) is determined as follows: Approximately 6-10 mg of sample is accurately weighed and sealed in an aluminum dish. Using a differential scanning calorimeter (DSC), the sample is heated from room temperature to 200°C at a rate of 10°C / min (first heating). After holding at 200°C for 10 minutes, it is cooled to -20°C at a rate of 10°C / min (first cooling). After holding at -20°C for 1 minute, the sample is heated again to 200°C at a rate of 10°C / min (second heating). The observed melting point (Tm) is the temperature of the peak of the melt peak. If more than two melt peaks are observed, the highest temperature at the peak of these peaks is taken as the melting point (Tm).
[0108] Polymer compositions (X) containing propylene polymers (B) with melting points within the above range exhibit excellent heat resistance, excellent flexibility, good transparency, and a moderately slow crystallization rate.
[0109] (B2) The percentage of isotactic five-unit components (mmmm) is over 80%.
[0110] The lower limit of the isotactic five-unit component ratio (mmmm) of the propylene polymer (B) is preferably 85% or more, more preferably 90% or more. Furthermore, the upper limit of the isotactic five-unit component ratio (mmmm) is not particularly limited, but as an option, 99.9% is preferred. That is, the isotactic five-unit component ratio (mmmm) is preferably 80-99.9%, more preferably 85-99.9%, and even more preferably 90-99.9%.
[0111] Polymer compositions (X) comprising propylene-based polymers (B) with isotactic five-unit component ratios (mmmm) satisfying the above-mentioned range exhibit high tensile strength and are therefore preferred. The content of the above-mentioned structural units can be determined using the methods described in the examples.
[0112] (B3) The crystallization temperature is 40~120℃, preferably 60~120℃, and more preferably 80~120℃.
[0113] If the crystallization temperature of the propylene polymer (B) is below the upper limit, the crystallinity of the 1-butene copolymer composition will not become excessively high, and it will have an appropriate crystallization rate. Therefore, when used as a hot melt adhesive, it can have a long open time for the purposes of this disclosure, which is preferred. Furthermore, if the crystallization temperature of the propylene polymer (B) is above the lower limit, the crystallinity will not become excessively low, which is preferred from the viewpoint of mechanical strength and heat resistance.
[0114] Regarding the crystallization temperature of the propylene polymer (B), the peak observed during the second cooling process of the differential scanning calorimeter will be taken as the crystallization temperature.
[0115] For propylene-based polymers (B), the melt flow rate (MFR) measured according to ASTM D1238 at a temperature of 230°C and a load of 2.16 kg is preferably 0.1 to 150 g / 10 min. More preferably, it is 1 to 100 g / 10 min, even more preferably, it is 2 to 100 g / 10 min, and particularly preferably, it is 3 to 50 g / 10 min.
[0116] If the MFR is above the lower limit, it exhibits good flowability and compatibility with other polymers containing copolymer (A). Adhesives such as hot melt adhesives containing propylene polymer (B) have good workability and are suitable for high-speed coating. If the MFR is below the upper limit, the propylene polymer (B) exhibits excellent mechanical properties, and molded articles containing propylene polymer (B) have excellent mechanical strength and impact resistance. For example, when used as an adhesive, it is preferred from the viewpoint of adhesive strength, heat resistance, and creep resistance.
[0117] Propylene polymers (B) include, for example, propylene homopolymers (homopolymer polypropylene) or copolymers of propylene with α-olefins having 2 to 20 carbon atoms other than propylene. The copolymers of propylene with the aforementioned α-olefins can be random copolymers (random polypropylene) or block copolymers (block polypropylene).
[0118] As one embodiment, the propylene polymer (B) is preferably a random copolymer (random polypropylene) or a block copolymer (block polypropylene), more preferably a random copolymer (random polypropylene).
[0119] Here, examples of α-olefins with 2 to 20 carbon atoms other than propylene include ethylene, 1-butene, 1-pentene, 1-hexene, 4-methyl-1-pentene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene, and 1-eicosene, with ethylene or α-olefins with 4 to 10 carbon atoms being preferred.
[0120] The above-mentioned α-olefins with 2 to 20 carbon atoms, excluding propylene, can be one type or more types.
[0121] The propylene-based polymer (B) may have at least one structural unit derived from a monomer derived from biomass. Examples of monomers derived from biomass include propylene from biomass, ethylene from biomass, and α-olefins from biomass with 4 to 20 carbon atoms. The same type of monomers constituting the polymer may be solely derived from biomass, solely derived from fossil fuels, or may include both monomers derived from biomass and monomers derived from fossil fuels.
[0122] For propylene-based polymers (B), it is preferred that the content of propylene-derived structural units (iv) is 65 mol% or more, and the content of structural units (v) derived from α-olefins with 2 to 20 carbon atoms other than propylene is 35 mol% or less (wherein the total content of structural units (iv) and structural units (v) is set to 100 mol%).
[0123] The lower limit of the content of propylene-derived structural units (iv) in the propylene polymer (B) is preferably 65 mol%, more preferably 70 mol%.
[0124] On the other hand, the upper limit of the content of the propylene-derived structural unit (iv) is preferably 100 moles.
[0125] The lower limit of the content of α-olefin-derived structural units (v) of propylene polymer (B) having 2 to 20 carbon atoms other than propylene is preferably 0 mol.
[0126] On the other hand, the upper limit of the content of structural units (v) derived from α-olefins with 2 to 20 carbon atoms other than propylene is preferably 35 mol%, and more preferably 30 mol%. The content of the above-mentioned structural units can be determined using the method described in the examples.
[0127] There are no particular limitations on the manufacturing method of propylene polymers (B), and known methods using known catalysts such as Ziegler-Natta catalysts and metallocene catalysts can be cited.
[0128] <Vinyl Polymers (C)> The polymer composition (X) may contain an ethylene polymer (C). The ethylene polymer (C) is a polymer other than the copolymer (A) and the propylene polymer (B), and the content of the ethylene-derived structural unit (vi) is 60 to 100 mol%.
[0129] The ethylene-based polymer (C) may have at least one structural unit derived from a monomer derived from biomass. Examples of monomers derived from biomass include ethylene derived from biomass and α-olefins derived from biomass with 3 to 20 carbon atoms. The same type of monomers constituting the polymer may be solely derived from biomass, solely derived from fossil fuels, or may include both monomers derived from biomass and monomers derived from fossil fuels.
[0130] The ethylene polymer (C) contained in the polymer composition (X) may be one or more.
[0131] By including ethylene-based polymers (C) in the polymer composition (X), it is easy to obtain molded articles with particularly excellent balance between impact resistance and transparency.
[0132] Specific examples of ethylene-based polymers (C) include high-pressure low-density polyethylene (C1) and ethylene-α-olefin copolymers (C2).
[0133] High-pressure processed low-density polyethylene (C1) As for high-pressure low-density polyethylene (C1), known high-pressure low-density polyethylenes can be used without restriction. High-pressure low-density polyethylene is generally polyethylene obtained by free radical polymerization of ethylene under high temperature and pressure. There are no particular limitations on its manufacturing method; for example, free radical polymerization under conditions of 500-2000 atmospheres and 150-300°C can be cited. Here, organic peroxides can be cited as polymerization initiators.
[0134] The preferred density of high-pressure low-density polyethylene (C1), measured according to ASTM D1505, is 900~925 kg / m³. 3 More preferably, it is 910~925 kg / m 3 A further preferred value is 915~920 kg / m³. 3 .
[0135] The melt flow rate (MFR) of high-pressure low-density polyethylene (C1), measured according to ASTM D1238 at 190°C and a load of 2.16 kg, is preferably 0.1 g / 10 min or more, more preferably 0.5 g / 10 min or more, particularly preferably 1.0 g / 10 min or more, preferably 50 g / 10 min or less, more preferably 30 g / 10 min or less, and particularly preferably 20 g / 10 min or less. That is, the above-mentioned melt flow rate (MFR) is preferably 0.1 to 50 g / 10 min, more preferably 0.5 to 30 g / 10 min, and particularly preferably 1.0 to 20 g / 10 min.
[0136] Ethylene-α-olefin copolymer (C2) The ethylene-α-olefin copolymer (C2) contains at least structural units (vi) derived from ethylene and structural units (vii) derived from α-olefins with 3 to 20 carbon atoms.
[0137] Ethylene-α-olefin copolymer (C2) is characterized by having fewer long-chain branched structures than high-pressure low-density polyethylene (C1), and is often sometimes referred to as linear low-density polyethylene (LLDPE).
[0138] The content of ethylene-derived structural units (vi) in the ethylene-α-olefin copolymer (C2) is preferably 60-99 mol%, more preferably 65-99 mol%, further preferably 70-99 mol%, and particularly preferably 80-99 mol%.
[0139] The content of structural units (vii) derived from α-olefins with 3 to 20 carbon atoms in the ethylene-α-olefin copolymer (C2) is preferably 1 to 40 mol%, more preferably 1 to 35 mol%, even more preferably 1 to 30 mol%, and particularly preferably 1 to 20 mol%.
[0140] Their content is relative to 100 mol% of the total structural units derived from ethylene and α-olefins with 3 to 20 carbon atoms.
[0141] The content of the above-mentioned structural units can be determined using the methods described in the examples.
[0142] If the content of structural units is within the above range, it is easy to obtain a molded body with excellent balance of impact resistance and softness.
[0143] Examples of α-olefins with 3 to 20 carbon atoms include propylene, 1-butene, 1-pentene, 3-methyl-1-butene, 1-hexene, 4-methyl-1-pentene, 1-heptene, 1-octene, 1-nonene, 1-decene, 1-undecene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene, 1-nonadecanene, and 1-eicosene. Among these, α-olefins with 3 to 10 carbon atoms are preferred, α-olefins with 3 to 8 carbon atoms are more preferred, propylene, 1-butene, and 1-octene are even more preferred, and propylene is particularly preferred.
[0144] The above-mentioned α-olefins with 3 to 20 carbon atoms can be one type or more types.
[0145] In addition to the structural units described above, the ethylene-α-olefin copolymer (C2) may contain one or more structural units derived from other polymerizable monomers without prejudice to the purpose of this disclosure.
[0146] Other polymerizable monomers include, for example, vinyl compounds such as styrene, vinylcyclopentene, vinylcyclohexane, and vinylnorbornene; vinyl esters such as vinyl acetate; unsaturated organic acids or their derivatives such as maleic anhydride; and non-conjugated polyenes such as dicyclopentadiene, cyclohexadiene, and 5-ethylidene-2-norbornene.
[0147] Specific examples of ethylene-α-olefin copolymers (C2) include ethylene-propylene copolymers, ethylene-1-butene copolymers, ethylene-propylene-ethylidene norbornene copolymers, ethylene-1-butene-1-octene copolymers, ethylene-4-methyl-1-pentene copolymers, ethylene-1-hexene copolymers, and ethylene-1-octene copolymers. Among these, ethylene-propylene copolymers and ethylene-1-butene copolymers are preferred.
[0148] The density of the ethylene-α-olefin copolymer (C2) is preferably 840 kg / m³. 3 The above, more preferably 850 kg / m 3 The above is further optimized to 855 kg / m³. 3The above is particularly preferred, with 860 kg / m³ being the optimal value. 3 The preferred value is 940 kg / m³. 3 The preferred value is 899 kg / m³. 3 The following is a further preferred value: 890 kg / m 3 The following is particularly preferred: 885 kg / m 3 The following applies. Specifically, the density is preferably 840~940 kg / m³. 3 More preferably, it is 850~899 kg / m 3 A further preferred value is 855~890 kg / m³. 3 The preferred strength is 860~885 kg / m³. 3 .
[0149] If the density is within the above range, it is easy to obtain a molded body with excellent balance of impact resistance, rigidity and transparency.
[0150] The density can be determined according to ASTM D1505 (density gradient tube method).
[0151] The MFR (measured according to ASTM D1238 at 190°C and 2.16 kg load) of the ethylene-α-olefin copolymer (C2) is preferably 0.01 g / 10 min or more, more preferably 0.1 g / 10 min or more, preferably 40 g / 10 min or less, more preferably 20 g / 10 min or less, and particularly preferably 10 g / 10 min or less.
[0152] If the MFR is within the above range, it is easy to obtain a molded body with excellent balance of impact resistance, rigidity and transparency.
[0153] For ethylene-α-olefin copolymers (C2), the MFR measured according to ASTM D1238 at 190°C and a load of 10 kg is... 10 The ratio of MFR2 to that measured at 190℃ and under a load of 2.16 kg (MFR 10 The MFR2 ratio is preferably 4.0 or higher, more preferably 5.0 or higher, more preferably 8.0 or lower, and even more preferably 7.0 or lower. That is, the ratio (MFR2) is... 10 The preferred value for MFR2 is 4.0 to 8.0, more preferably 5.0 to 7.0.
[0154] If MFR 10 Within the above range, / MFR2 can easily produce molded parts with excellent balance between transparency and impact resistance.
[0155] Ethylene-α-olefin copolymers (C2) can be manufactured by conventional methods using vanadium-based catalysts, titanium-based catalysts, or metallocene catalysts. The use of metallocene catalysts is preferred, as it yields copolymers with narrow molecular weight or compositional distributions, and is even more desirable from the perspective of mechanical properties, transparency, or impact resistance.
[0156] The above MFR 10 MFR2 can be determined using the methods described in the examples.
[0157] <Polymer Composition (X)> Examples of polymer compositions (X) include: compositions comprising copolymer (A) and propylene polymer (B); compositions comprising copolymer (A), propylene polymer (B) and high-pressure low-density polyethylene (C1); compositions comprising copolymer (A), propylene polymer (B) and ethylene-α-olefin copolymer (C2); compositions comprising copolymer (A), propylene polymer (B), high-pressure low-density polyethylene (C1) and ethylene-α-olefin copolymer (C2); compositions comprising copolymer (A) and high-pressure low-density polyethylene (C1); and compositions comprising copolymer (A) and ethylene-α-olefin copolymer (C2).
[0158] The polymer composition (X) preferably satisfies one or more of the following requirements (X1) to (X4), and more preferably satisfies the following requirements (X1-2) or (X1-3).
[0159] [Requirements (X1)] As a preferred method of this disclosure, it includes: (X1-1) A polymer composition (X) having a content of 1-butene-propylene-ethylene copolymer (A) greater than 36% by mass and less than 99% by mass, and a content of propylene polymer (B) greater than 1% by mass and less than 64% by mass (wherein, the total of 1-butene-propylene-ethylene copolymer (A) and propylene polymer (B) is set as 100% by mass). (X1-2) A polymer composition (X) comprising 1 to 36% by mass of 1-butene-propylene-ethylene copolymer (A) and 64 to 99% by mass of propylene polymer (B) (wherein the total of 1-butene-propylene-ethylene copolymer (A) and propylene polymer (B) is set at 100% by mass). (X1-3) A polymer composition (X) comprising 1-butene-propylene-ethylene copolymer (A) of 1-50% by mass, propylene polymer (B) of 30-98% by mass, and ethylene polymer (C) of 1-20% by mass (wherein the total of 1-butene-propylene-ethylene copolymer (A), propylene polymer (B), and ethylene polymer (C) is set at 100% by mass).
[0160] [Requirements (X1-1)] Preferably, the content of copolymer (A) is higher than 36% by mass and lower than 99% by mass, and the content of propylene polymer (B) is higher than 1% by mass and lower than 64% by mass (wherein, the total of copolymer (A) and propylene polymer (B) is set to 100% by mass). More preferably, the content of copolymer (A) is higher than 36% by mass and lower than 97% by mass, and the content of propylene polymer (B) is higher than 3% by mass and lower than 64% by mass. Further preferably, the content of copolymer (A) is 38 to 95% by mass, and the content of propylene polymer (B) is 5 to 62% by mass. More preferably, the content of copolymer (A) is 45 to 95% by mass, and the content of propylene polymer (B) is 5 to 55% by mass. Particularly preferably, the content of copolymer (A) is 75 to 95% by mass, and the content of propylene polymer (B) is 5 to 25% by mass.
[0161] For polymer compositions (X) that include copolymer (A) and propylene polymer (B) within the aforementioned range, copolymer (A) and propylene polymer (B) have good compatibility, heat resistance, and promote crystallization. By using copolymer (A) as the main component, the slow crystallization rate of copolymer (A) is retained, and crystallization is promoted by propylene polymer (B), thereby improving the granulation properties and facilitating processing into granules.
[0162] For example, in hot melt adhesives, when the content of copolymer (A) in the polymer composition (X) is above the lower limit, the softness is excellent, the adhesive has excellent flexibility and surface conformability, and the open time is longer. When it is below the upper limit, the mechanical strength and heat resistance of the composition are excellent, and the adhesive strength and creep resistance at high temperatures of the obtained adhesive are improved.
[0163] Furthermore, the fact that the polymer composition (X) can be processed into granules also facilitates its use as a modifier for various molded articles in general-purpose molding machines. When used as a modifier, if the content of copolymer (A) in the polymer composition (X) is above the lower limit, the modification effect on flexibility is excellent. If it is below the upper limit, granulation becomes easier, and in addition, the mechanical strength and heat resistance of the composition are improved.
[0164] [Requirements (X1-2)] The preferred copolymer (A) content is 1-36% by mass, and the propylene polymer (B) content is 64-99% by mass (wherein the total of copolymer (A) and propylene polymer (B) is set to 100% by mass); more preferably, the copolymer (A) content is 3-32% by mass, and the propylene polymer (B) content is 68-97% by mass; even more preferably, the copolymer (A) content is 5-27% by mass, and the propylene polymer (B) content is 73-95% by mass; particularly preferably, the copolymer (A) content is 5-25% by mass, and the propylene polymer (B) content is 75-95% by mass.
[0165] If the content of copolymer (A) in the polymer composition (X) of the molded body is within the above range, while giving full play to the mechanical strength (flexural properties, tensile strength, etc.) and heat resistance of the propylene polymer (B), a molded body with moderate softness, excellent impact resistance and transparency can be easily obtained due to the copolymer (A).
[0166] [Requirements (X1-3)] In the case of a polymer composition (X) having three components: copolymer (A), propylene polymer (B), and ethylene polymer (C), it is preferable that the content of copolymer (A) is 1-50% by mass, the content of propylene polymer (B) is 30-98% by mass, and the content of ethylene polymer (C) is 1-20% by mass (wherein, the total of copolymer (A), propylene polymer (B), and ethylene polymer (C) is set to 100% by mass); more preferably, the content of copolymer (A) is 5-40% by mass, the content of propylene polymer (B) is 42-92% by mass, and the content of ethylene polymer (C) is 3-18% by mass; even more preferably, the content of copolymer (A) is 8-35% by mass, the content of propylene polymer (B) is 48-88% by mass, and the content of ethylene polymer (C) is 4-17% by mass.
[0167] If the content of copolymer (A) in the polymer composition (X) of the molded article is within the above-mentioned range, while leveraging the mechanical strength (flexural strength, tensile strength, etc.) and heat resistance of the propylene polymer (B), a molded article with moderate softness and excellent impact resistance can be easily obtained due to the copolymer (A) and the ethylene polymer (C). In particular, compared with the propylene polymer (B), the ethylene polymer (C) has a lower glass transition temperature, which can improve the impact resistance at low temperatures, and also contributes to the improvement of moldability.
[0168] [Requirement (X2)] Using a differential scanning calorimeter (DSC), the temperature was lowered from room temperature to -70°C at a cooling rate of 20°C / min (first cooling), held at -70°C for 5 minutes, then heated from -70°C to 200°C at a heating rate of 20°C / min (first heating), held at 200°C for 10 minutes, then further lowered to -70°C at a cooling rate of 20°C / min (second cooling), held at -70°C for 1 minute, and then heated again from -70°C to 200°C at a heating rate of 20°C / min (second heating). In the above measurements, the high-temperature peak (crystallization temperature) generated during the second cooling was above 40°C and below 110°C, the first peak (melting peak) generated during the second heating was above 20°C and below 100°C, and the second peak (melting peak) was between 100°C and 170°C.
[0169] For the polymer composition (X), in the DSC curve obtained by the second heating of the differential scanning calorimeter (DSC) described above, it is preferable that the melting peak has at least the first peak and the second peak.
[0170] Here, the first peak refers to the peak below 100°C in the DSC curve. The upper limit of the first peak is preferably below 100°C, more preferably below 80°C, and even more preferably below 70°C. On the other hand, the lower limit of the first peak is preferably above 20°C, more preferably above 25°C, and even more preferably above 30°C. That is, the first peak is preferably above 20°C and below 100°C, more preferably 25~80°C, and even more preferably 30~70°C.
[0171] The first peak is the melting peak originating from copolymer (A). There can be more than two first peaks. That is, there can be more than two melting peaks in the range below 100°C.
[0172] The second peak refers to a peak located in the range of 100°C or higher. The upper limit of the second peak is preferably 170°C or lower, more preferably 168°C or lower, and even more preferably 165°C or lower. On the other hand, the lower limit of the second peak is preferably 100°C or higher, more preferably 105°C or higher, and even more preferably 110°C or higher. That is, the second peak is preferably 100~170°C, more preferably 105~168°C, and even more preferably 110~165°C.
[0173] The second peak is a melting peak originating from the propylene-based polymer (B). More than two second peaks can exist; that is, more than two melting peaks can exist in the temperature range above 100°C.
[0174] The reason why a melting peak from the 1-butene polymer, which is not observed in the copolymer (A), is observed in the polymer composition (X) is not necessarily clear. However, it is believed that by properly controlling the ethylene-derived structural units of the copolymer (A), good compatibility with the propylene polymer (B) contained in the polymer composition (X) is achieved, and the crystallization of the copolymer (A) is promoted by including a small amount of propylene polymer (B).
[0175] [Requirements (X3)] The Shore A hardness measured according to ASTM D2240 is preferably 30~99, more preferably 40~99, even more preferably 50~98, and more preferably 60~97.
[0176] [Requirement (X4)] The preferred Shore D hardness, measured according to ASTM D2240, is below 80.
[0177] If the Shore A hardness or Shore D hardness is below the upper limit, the crystallinity is low, resulting in excellent softness and improved flexibility and deformation following properties as a hot melt adhesive. If the enthalpy of fusion is above the lower limit, the mechanical properties are excellent. When used as a hot melt adhesive, the bond strength is improved.
[0178] Especially when softness is required, the Shore D hardness is preferably 20 to 70, and more preferably 20 to 43.
[0179] Furthermore, when excellent mechanical properties are required, the Shore D hardness is preferably 44 to 80, and more preferably 44 to 70.
[0180] There are no particular limitations on the melt flow rate (MFR) of the polymer composition (X) measured in accordance with ASTM D1238 at 230°C and 2.16 kg load, but it is preferably 0.1 to 100 g / 10 min.
[0181] If the MFR is above the lower limit mentioned above, the polymer composition (X) exhibits good flowability and operability, making it suitable for high-speed coating. If the MFR is below the upper limit mentioned above, the polymer composition (X) exhibits excellent mechanical strength and good granulation properties. Due to its excellent mechanical strength, the adhesive strength as a hot melt adhesive is improved, and the durability as a packaging material is enhanced. If the MFR is above the lower limit mentioned above, the polymer composition (X) exhibits excellent flowability, good coating properties as a hot melt adhesive, and facilitates the molding of various molded parts.
[0182] Especially when fluidity is required, the MFR is preferably 20~100g / 10min, more preferably 30~50g / 10min.
[0183] In addition, where excellent mechanical strength is required, the MFR is preferably 1g / 10min or more and less than 30g / 10min.
[0184] For the polymer composition (X), the enthalpy of fusion ΔHfus in the second peak, measured during the second heating of the differential scanning calorimeter (DSC), is 5~100 J / g, preferably 5~90 J / g, more preferably 5~85 J / g, and even more preferably 5~80 J / g.
[0185] The enthalpy of melting becomes an indicator of crystallinity. If the enthalpy of melting is below the upper limit, molded articles with low crystallinity and excellent flexibility can be easily obtained. Furthermore, when used as a hot melt adhesive, flexibility and deformation conformity are improved. If the enthalpy of melting is above the lower limit, molded articles with excellent mechanical properties and heat resistance can be easily obtained. Furthermore, when used as a hot melt adhesive, bond strength and creep resistance at high temperatures are improved.
[0186] The haze of the polymer composition (X), as measured according to JIS K7136:2000, is 50% or less, preferably 45% or less, and more preferably 30% or less. If the haze of the polymer composition (X) is within the above range, it has good transparency and is suitable as an adhesive or packaging material for applications requiring design flexibility.
[0187] One embodiment of this composition includes a polymer composition containing a copolymer (A) and a propylene polymer (B); and a polymer composition containing a copolymer (A), a propylene polymer (B), and a vinyl polymer (C). The copolymer (A) and the propylene polymer (B) have good compatibility, thus the polymer compositions of the embodiments can provide polymer compositions with excellent flexibility and high tensile strength. Furthermore, the polymer compositions can form layers or films with excellent balance in heat resistance, tensile strength, and resistance to whitening during secondary processing such as deep drawing, and are therefore suitable for applications such as shrink films, breathable films, adhesive films, engineering films, skin materials, automotive interior trim materials, seals, and gasket materials.
[0188] <Additives> The polymer composition (X) may also contain additives. Examples of additives include, for instance, conventionally known flow modifiers, crystal nucleating agents, antioxidants, heat stabilizers, weather stabilizers such as UV absorbers and light stabilizers, hydrochloric acid absorbers, pigments, dyes, antibacterial agents, fungicides, antistatic agents, lubricants, slip agents, anti-blocking agents, anti-glare agents, foaming agents, foaming aids, plasticizers such as mineral oils, and fillers. The polymer composition (X) may contain one additive, or two or more additives, and may also contain additives to the extent that they do not prejudice the purpose of this disclosure.
[0189] <Method for manufacturing polymer composition (X)> The method for manufacturing the polymer composition (X) is not particularly limited. For example, it can be prepared by mixing the copolymer (A), the propylene polymer (B), and / or the ethylene polymer (C), and any other components as needed, in the above-described proportions using, for example, a Henschel mixer, a V-type mixer, a belt mixer, a drum mixer, a kneading extruder, etc. Alternatively, it can be prepared by melt-blending using a single-screw extruder, a twin-screw extruder, a kneader, a Banbury mixer, etc., either after mixing or without mixing. Furthermore, granulation, pulverization, etc., can be performed as needed.
[0190] When mixing and compounding them, the components can be added all at once or in stages.
[0191] There are no particular limitations on the melt mixing method, and commercially available melt mixing equipment such as extruders can be used. For example, the temperature of the mixing section in the melt mixing equipment is typically 120~250°C, preferably 120~230°C. The mixing time is typically 0.5~30 minutes, particularly preferably 0.5~5 minutes.
[0192] Copolymer (A), polymer composition (X) comprising copolymer (A) and propylene polymer (B), polymer composition (X) comprising copolymer (A) and ethylene polymer (C), or polymer composition (X) comprising copolymer (A), propylene polymer (B), and ethylene polymer (C) can be suitably used as granules, hot melt adhesives, coating agents, and skin materials. The hot melt adhesive can be used in automotive parts such as interior and exterior trim components. Additionally, molded articles comprising polymer composition (X) can also be used in films, sheets, packaging materials using them, nonwoven fabrics, seals, cover liner materials, foams, and automotive parts such as interior and exterior trim components.
[0193] Hot melt adhesive Examples of uses for the copolymer (A) or this composition include hot melt adhesives. The hot melt adhesive disclosed herein can be obtained, for example, by methods such as: sequentially melting and mixing the components in a melt-melting tank, preferably under vacuum and nitrogen flow, by rotating stirring blades; melting and mixing by applying shear under heating using the double-rotating blades of a kneader; or melting and mixing using the screw of a single-screw or twin-screw extruder. The temperature is typically adjusted within a range of 120–230°C, preferably 150–200°C. Bundles or granules thus prepared can be used for various applications.
[0194] In the case of hot melt adhesives, the adhered objects can be bonded before the adhesive cures, or the temporarily cured hot melt adhesive can be reheated to reactivate it before bonding the adhered objects. Examples of the shape of such temporarily cured hot melt adhesives include sheets, films, non-woven fabrics, small flakes, and rods.
[0195] In hot melt adhesives, the content of copolymer (A) is typically 1 to 90% by mass, preferably 3 to 50% by mass, and more preferably 5 to 40% by mass, relative to the total amount of adhesive. If the content is within the above range, it is preferred from the viewpoint of the balance between the adhesive strength and the coatability of the hot melt adhesive.
[0196] Hot melt adhesives may contain non-crystalline polyalphaolefins (APAO) as needed.
[0197] The melt viscosity of APAO is preferably 500~200,000 mPa·s / 190°C, more preferably 1,000~50,000 mPa·s / 190°C. If the melt viscosity is 500 mPa·s / 190°C or higher, sufficient cohesive force can be obtained, and the adhesive strength of the adhesive is improved. On the other hand, if the melt viscosity is 200,000 mPa·s / 190°C or lower, workability is improved when applying the hot melt adhesive, and therefore this is preferred.
[0198] As components of such APAO, there are various compositions. For example, there are homopolymers or copolymers such as atactic polypropylene and atactic poly-1-butene, or copolymers or terpolymers of propylene, ethylene, 1-butene, etc., propylene homopolymers, propylene-butene copolymers, propylene-ethylene copolymers, etc.
[0199] The copolymer (A) contains a large amount of 1-butene as a structural unit and has excellent compatibility with propylene-based polymers. Therefore, it also has excellent compatibility with APAO, which uses propylene and 1-butene, and can be used appropriately.
[0200] Specific examples of APAO include REXtac LLC.'s RT2730 (melt viscosity at 190°C: 4,000 mPa·s) and VESTOPLAST 704 (product name, manufactured by Evonik, melt viscosity (190°C): 3,500 mPa·s).
[0201] APAO can be used alone or in combination with two or more types.
[0202] In hot melt adhesives, the content of APAO, relative to the total amount of adhesive, is typically 1 to 99% by mass, preferably 10 to 90% by mass, and more preferably 20 to 80% by mass. Content within the above range is preferred from the viewpoint of the uniformity of adhesive strength and coatability of the hot melt adhesive.
[0203] Hot melt adhesives may contain tackifiers as needed.
[0204] Examples of tackifiers include, for instance, at least one resin selected from natural rosin, modified rosin, polyterpene resins, synthetic petroleum resins, coumarone resins, phenolic resins, xylene resins, styrene resins, low molecular weight styrene resins, and isoprene resins. Among these, rosin resins, polyterpene resins, and synthetic petroleum resins are preferred, and tackifiers having aliphatic and / or alicyclic structures are even more preferred.
[0205] Here, regarding substances particularly preferred for petroleum resins having aliphatic and / or alicyclic structures, examples of rosin-based resins include partially and fully hydrogenated rosin and their derivatives; examples of polyterpene-based resins include homopolymers or copolymers of cyclic terpenes; and examples of synthetic petroleum resins include aliphatic petroleum resins, alicyclic petroleum resins, aliphatic-alicyclic copolymers, and hydrogenated copolymers of petroleum naphtha oil and various terpenes.
[0206] As a tackifier, a tackifier with a softening point of 25 to 160°C is preferred. If the softening point is above 25°C, it can prevent seepage to the surface; if the softening point is below 160°C, the viscosity during melting will not become excessively high, resulting in good processability. Specifically, the trade names "ARKON P-70", "ARKON P-90", "ARKON P-100", "ARKON P-115", "ARKON P-125", and "ARKON P-140" (all manufactured by Arakawa Chemical Industry Co., Ltd.) can be appropriately used.
[0207] A single adhesive can be used alone, or two or more can be used together.
[0208] In hot melt adhesives, the content of the tackifier, when used relative to the total amount of adhesive, is typically 1 to 70% by mass, preferably 5 to 50% by mass, and more preferably 10 to 40% by mass. If the content is within the above range, it can impart flowability and adhesiveness without reducing the adhesive strength, and is therefore preferred.
[0209] Hot melt adhesives may contain wax as needed.
[0210] Examples of waxes include synthetic waxes such as Fischer-Tropsch wax, polyethylene wax, and polypropylene wax; petroleum waxes such as paraffin wax and microcrystalline wax; and natural waxes such as wood wax, carnauba wax, and beeswax. The copolymer (A) has excellent compatibility with polypropylene, therefore polypropylene wax is particularly preferred.
[0211] The type B viscosity (190°C) of the wax is preferably 10~8000 mPa·s, more preferably 100~5000 mPa·s. If the type B viscosity is within the above range, it is preferred from the perspective of cohesiveness and processability.
[0212] The melting point of the wax, as measured by DSC, is preferably 80-150°C, more preferably 90-140°C. If the melting point is within the above range, it is preferable in terms of flexibility and processability when using the adhesive.
[0213] Commercially available waxes include, for example, “Mitsui Hi-WAX 420P”, “Mitsui Hi-WAX NL100”, and “Mitsui Hi-WAX NP015” (all manufactured by Mitsui Chemicals Co., Ltd.).
[0214] One type of wax can be used alone, or two or more types can be used together.
[0215] In hot melt adhesives, the content of wax, when used, is typically 1 to 60% by mass, preferably 1 to 50% by mass, and more preferably 1 to 40% by mass, relative to the total amount of adhesive. If the content is within the above range, flowability and heat resistance can be imparted without reducing adhesive strength, and therefore this is preferred.
[0216] In hot melt adhesives, at least one additive selected from conventionally known flow modifiers, nucleating agents, antioxidants, heat stabilizers, ultraviolet absorbers, light stabilizers, pigments, dyes, antibacterial agents, mildew inhibitors, antistatic agents, foaming agents, foaming aids, mineral oils, and other plasticizers and fillers may be added as needed, without prejudice to the purpose of this disclosure.
[0217] Regarding the application of hot melt adhesives, there are no particular restrictions as long as the purpose of this disclosure is achieved, and commercially available hot melt applicators can be widely used. Examples of hot melt applicators include slot coaters, roller coaters, spiral coaters capable of spiral coating, Omega coaters capable of wavy coating, control seam applications, slot spray coaters capable of surface coating, curtain spray coaters, dot coaters capable of dot coating, and droplet coaters capable of linear coating. A particularly preferred application for hot melt adhesives is the bonding of corrugated paper to each other.
[0218] As a method for using the hot melt adhesive of this disclosure as a hot melt adhesive, there are the following bonding methods: using a screw extruder having a die section called a T-die method, blow molding method, calendering method, or spinning method, the obtained hot melt adhesive is formed into a sheet, film, or non-woven fabric shape, fixed in the middle of the objects to be laminated, and then heat-bonded; or the adhesive, which has been formed into a sheet shape, is heated and melted on one object to be laminated, and the other object to be laminated is directly pressed together while cooling. Additionally, there are the following methods: using the aforementioned screw extruder to melt the hot melt adhesive of this disclosure, and directly inserting the adhesive between the objects to be laminated without performing the molding process described above, and then heat-bonding; or, if one object to be laminated is a thermoplastic, directly bonding by co-extrusion, or directly coating it onto one object to be laminated and then heat-bonding again.
[0219] Hot melt adhesives are suitable for bonding, for example, substrates formed of polyolefin resins to each other, bonding the substrates to metal materials (e.g., metal plates, metal foils, metal mesh) or other raw materials (e.g., nonwoven fabrics, textiles, cloth, corrugated paper, etc., glass), and bonding the metal materials or other raw materials to each other. They are particularly suitable for bonding corrugated paper to other adhered materials, or bonding corrugated paper to corrugated paper.
[0220] Examples of resin sheets formed from polyolefin resins, etc., include single-layer or laminated resin sheets of polyolefin resins (e.g., polyethylene, polypropylene), polyester resins, polycarbonate resins, polyarylate resins, acrylic resins, polyphenylene sulfide resins, polystyrene resins, vinyl resins, vinyl chloride resins, polyimide resins, epoxy resins, etc.
[0221] Coating Agent As a coating agent in this disclosure, there are no particular limitations; for example, a coating agent prepared by dissolving or dispersing a copolymer (A) or a polymer composition (X) using the copolymer (A) in an organic solvent may be cited. The coating agent comprises a copolymer (A) or a polymer composition (X).
[0222] Examples of organic solvents include, for example, aromatic hydrocarbons such as benzene, toluene, and xylene; aliphatic hydrocarbons such as hexane, heptane, octane, and decane; alicyclic hydrocarbons such as cyclohexane, cyclohexene, methylcyclohexane, ethylcyclohexane, and decahydronaphthalene; alcohols such as methanol, ethanol, isopropanol, butanol, pentanol, hexanol, and propylene glycol; ketone solvents such as acetone, methyl isobutyl ketone, methyl ethyl ketone, pentanol, hexanone, isophorone, and acetophenone; cellosols such as methyl cellosol and ethyl cellosol; esters such as methyl acetate, ethyl acetate, butyl acetate, methyl propionate, and butyl formate; and halogenated hydrocarbons such as trichloroethylene, dichloroethylene, and chlorobenzene. One or more organic solvents may be used.
[0223] There are no particular restrictions on the content of organic solvents in the coating agent. For example, it can be more than 30% by mass or more than 40% by mass. Alternatively, it can be less than 90% by mass or less than 80% by mass.
[0224] The coating agent can be used as, for example, an adhesive or heat sealant for metals, an adhesive or heat sealant for polyolefins, or an adhesive or heat sealant for metals and polyolefins. It can also be used as an adhesive for PTP (press-through pack) packaging, an adhesive for lamination, a raw material for coatings, or a raw material for primers. It is particularly suitable when at least one of the adhered materials is a plastic material, and among plastic materials, polyolefin materials, especially polybutene-based materials and polypropylene-based materials, are preferred.
[0225] [Molded body] Various molded articles formed from copolymers (A), polymer compositions (X) comprising copolymers (A) and propylene polymers (B), polymer compositions (X) comprising copolymers (A) and ethylene polymers (C), or polymer compositions (X) comprising copolymers (A), propylene polymers (B), and ethylene polymers (C) can be widely used in previously known applications of polyolefins. These molded articles are obtained by known thermoforming methods such as extrusion molding, injection molding, blow molding, blow molding, extrusion blow molding, injection blow molding, compression molding, vacuum forming, powder slush molding, calendering, and foam molding.
[0226] <membrane> The film containing the copolymer (A) or the polymer composition (X) using the copolymer (A) can be a stretched film or an unstretched film, preferably an unstretched film.
[0227] The aforementioned unstretched film is acceptable as long as it is not stretched; there are no particular limitations. The shape, size (thickness), etc., can be appropriately selected according to the desired application. Furthermore, the unstretched film can be a single layer or multiple layers. In the case of multiple layers, at least one layer must be a film containing a copolymer (A) or the aforementioned polymer composition (X). This includes films obtained by co-extrusion using known multilayer film forming methods such as T-die molding or blown film molding, or films obtained by further laminating layers containing copolymer (A) or the aforementioned polymer composition (X) onto a pre-formed substrate. There are no particular limitations on the substrate; sometimes it is a metal such as aluminum plate, steel plate, or stainless steel plate, and sometimes it is a thermoplastic resin. It should be noted that when the aforementioned unstretched film is multilayered, it means that all its layers are unstretched.
[0228] The thickness of the unstretched film (total thickness in the case of multiple layers) is preferably 5 μm or more, more preferably 10 μm or more, preferably 150 μm or less, and more preferably 100 μm or less.
[0229] It should be noted that this specification does not specifically distinguish between membranes and sheets. However, generally, membranes refer to membrane-like bodies with a thickness of less than 250 μm, while sheets refer to thin plate-like bodies with a thickness of more than 250 μm.
[0230] Membranes can be used as, for example, stretch membranes, shrink membranes, breathable membranes, adhesive membranes, and engineering membranes.
[0231] <Sheet> There are no particular limitations on the sheet material described above; its shape, size (thickness), etc., can be appropriately selected according to the intended application. Furthermore, the sheet material can be single-layered or multi-layered. In the case of multi-layered sheets, at least one layer must be a sheet containing the copolymer (A) or the aforementioned polymer composition (X).
[0232] The thickness of the sheet (total thickness in the case of multiple layers) is preferably 250~2000μm, more preferably 250~1500μm.
[0233] Specific uses of the aforementioned sheet include, for example, packaging sheets for packaging food, liquids, pharmaceuticals, etc., and containers formed from the sheet (e.g., trays, cups obtained by thermoforming the sheet, containers obtained by bending the sheet).
[0234] <Injection Molded and Blow Molded Products> The molded body in this disclosure may also be an injection-molded body, for example. There are no particular limitations on the injection-molded body; for example, examples include molded bodies manufactured by injection molding to a desired shape using conventionally known injection molding apparatus and under known conditions.
[0235] Injection molded parts can be widely used in applications such as interior trim materials for automobiles, exterior trim parts for automobiles, and housings, containers, tubes, or pipes for household appliances.
[0236] The molded body in this disclosure may also be a blow-molded body, for example. There are no particular limitations on the blow-molded body. For example, a molded body manufactured by blow molding into a desired shape using a conventionally known blow molding apparatus and under known conditions can be cited as an example.
[0237] The blow-molded body may also be a multilayer molded body, for example. In this case, at least one layer of the multilayer molded body is a layer containing the copolymer (A) or the composition thereof.
[0238] Specific applications of injection-molded and blow-molded bodies include, for example, food containers, beverage containers, lids, pharmaceutical containers, various other containers, housings for daily necessities and household appliances, automotive parts, pipes, and conduits. Examples of daily necessities include, for example, clothes organizers, buckets, washbasins, stationery such as writing instruments, containers, toys, cooking utensils, and various other boxes.
[0239] <Sealing membrane> As an example of the above-mentioned molded body, a sealing film can be cited.
[0240] The sealing film described above has at least one layer formed by this composition (hereinafter also referred to as "layer (X)"). The sealing film may be a single layer or a multilayer of two or more layers. In this case, the composition is preferably a polymer composition containing 1-butene-propylene-ethylene copolymer (A) and propylene polymer (B), or a polymer composition containing 1-butene-propylene-ethylene copolymer (A), propylene polymer (B) and ethylene polymer (C).
[0241] The sealing film described above may have two or more layers (X). The sealing film may also have layer (X) and layers other than layer (X). The sealing film may also have two or more of the aforementioned other layers.
[0242] In this specification, no special distinction is made between membranes and sheets. However, generally, membranes refer to membrane-like bodies with a thickness of less than 250 μm, while sheets refer to thin plate-like bodies with a thickness of more than 250 μm.
[0243] The shape, size, and thickness of the sealing film can be appropriately selected according to the desired application. The sealing film can be either a stretched film or an unstretched film, but an unstretched film is preferred. In the case of a multi-layered unstretched film, "unstretched" means that all its layers are not stretched.
[0244] Unstretched membranes are any membranes that are not stretched; there are no particular restrictions. The shape, size, and thickness can be appropriately selected based on the intended application. Unstretched membranes can be single-layered or multi-layered (two or more layers). In the case of multi-layered unstretched membranes, at least one layer must be layer (X). That is, an unstretched membrane can be a single-layered or multi-layered membrane formed solely of layer (X), or it can be a laminate containing layer (X) and a substrate. Specific examples of the substrate will be described later.
[0245] The thickness of the sealing film or unstretched film (in the case of a multilayer film, the total thickness of each layer) is preferably 5 μm or more, more preferably 10 μm or more, even more preferably 20 μm or more, preferably 150 μm or less, more preferably 130 μm or less, even more preferably 100 μm or less, for example, 5 to 150 μm.
[0246] Specific uses of sealing films or unstretched films include, for example, packaging films used for packaging food, liquids, pharmaceuticals or electronic components, and packaging materials derived therefrom.
[0247] The aforementioned sealing film or unstretched film can be manufactured, for example, using at least the present composition and using conventionally known single-layer or multi-layer film forming machines. The method of manufacturing the unstretched film is not particularly limited as long as it does not prejudice the purpose of this disclosure. Unstretched films include films obtained by co-extrusion using known multi-layer film forming methods such as T-die film forming and blown film forming, and films obtained by further laminating layers (X) on a pre-formed substrate. The unstretched film can, for example, be a film obtained by a manufacturing method including the following steps: laminating a single-layer or multi-layer film (e.g., a single-layer or multi-layer film formed only of layer (X)) to a substrate using any method selected from the group consisting of melt extrusion lamination, hot lamination, and dry lamination.
[0248] <Layered Body> As an example of the above-mentioned molded body, a laminated body can be cited.
[0249] The above-described laminate has a substrate and a layer (layer (X)) formed from the composition. In this case, the composition is preferably a polymer composition containing a 1-butene-propylene-ethylene copolymer (A) and a propylene polymer (B), or a polymer composition containing a 1-butene-propylene-ethylene copolymer (A), a propylene polymer (B), and an ethylene polymer (C).
[0250] In one embodiment, the laminate includes a substrate and a sealing film. For example, in the laminate, the substrate and the sealing film are laminated together.
[0251] Examples of substrates include resin films, metal foils, paper, and vapor-deposited films. Examples of resins constituting the resin film include thermoplastic resins, specifically polyolefin resins (e.g., polyethylene, polypropylene), polystyrene resins, polyester resins (e.g., polyethylene terephthalate (PET)), polyamide resins, polyimide resins, polycarbonate resins, polyarylate resins, acrylic resins, polyphenylene sulfide resins, ethylene resins, vinyl chloride resins, and epoxy resins. The resin film can be a single layer or a multilayer of two or more layers. The resin film can be a stretched film or an unstretched film. Examples of metal foils include aluminum foil, steel foil, and stainless steel foil, with aluminum foil being preferred.
[0252] As a substrate, it is preferably selected from at least one of the following groups: polyolefin film, polystyrene film, polyester film, polyamide film, laminated film of polyolefin film and gas barrier resin film, metal foil such as aluminum foil, paper, and vapor-deposited film.
[0253] The aforementioned laminate can be manufactured, for example, using conventionally known single-layer or multi-layer film forming machines. The aforementioned laminate can be manufactured, for example, by a manufacturing method including the following steps: laminating a substrate to the aforementioned sealing film using any method selected from the group consisting of melt extrusion lamination, hot lamination, and dry lamination. The aforementioned laminate can be manufactured, for example, by a manufacturing method including the following steps: laminating a substrate to a single-layer or multi-layer film formed solely of layer (X) using any method selected from the group consisting of melt extrusion lamination, hot lamination, and dry lamination.
[0254] The laminate itself can also be used as a sealing film. In this case, the substrate is preferably a resin film, and more preferably an unstretched film. That is, the sealing film can be a single-layer or multi-layer film formed only by layer (X), or it can be a laminate having layer (X) and substrate.
[0255] The aforementioned sealing film and the aforementioned laminate exhibit excellent resistance to whitening during stretching, as well as good heat resistance and tensile strength. Therefore, the characteristics of the sealing film can be utilized to make it suitable for use as packaging for all kinds of items, such as daily necessities, food (food packaging materials), liquids, pharmaceuticals, electronic components, and building materials.
[0256] The aforementioned sealing film or laminate can be incorporated into energy storage devices such as lithium-ion batteries and lithium-ion capacitors. The aforementioned sealing film or laminate can be suitably used, for example, as a packaging for lithium-ion batteries. Alternatively, this disclosure can be said to provide an energy storage device comprising this composition. Examples of such energy storage devices include, for instance, an energy storage device comprising the aforementioned sealing film or laminate; a specific example is a packaging for a lithium-ion battery comprising the aforementioned sealing film or laminate.
[0257] Lithium-ion batteries typically contain a positive electrode, a negative electrode, a separator between the positive and negative electrodes, and a non-aqueous electrolyte. The positive electrode typically includes a positive current collector formed of a metallic or carbon material, and a positive electrode active material, such as a composite oxide formed of lithium and a transition metal, capable of absorbing and releasing lithium ions. The negative electrode typically includes a negative current collector formed of a carbon material, and a negative electrode active material, such as metallic lithium, lithium-containing alloys, or metals or alloys capable of alloying with lithium, capable of absorbing and releasing lithium ions. The non-aqueous electrolyte includes a lithium salt as the electrolyte and a non-aqueous solvent. In lithium-ion batteries, the positive electrode, negative electrode, and separator are impregnated with a non-aqueous electrolyte. Details regarding the non-aqueous solvent will be described later in the section on <Non-Aqueous Solvents>.
[0258] In most cases, lithium-ion batteries have a packaging body (lithium-ion battery packaging body) at their periphery. Inside this packaging body are sealed a positive electrode, a negative electrode, a separator, and a non-aqueous electrolyte. Typically, a positive terminal and a negative terminal are connected to the positive and negative electrodes, respectively. A portion of the positive terminal and a portion of the negative terminal protrude outside the packaging body.
[0259] The following describes the use of the aforementioned sealing film or laminate as the packaging body. A lithium-ion battery is obtained by thermally fusing the positive and negative electrodes, etc., with a portion of the positive and negative terminals exposed to the outside of the pair of sealing films or the pair of laminates, at the periphery of these films or laminates. When using the aforementioned laminate as the packaging body, the laminate may also have a substrate made of a metal such as aluminum foil.
[0260] Lithium-ion batteries using lithium-ion battery packaging can be used in, for example, portable electronic devices, personal computers, robots, drones, automobiles, aircraft, wearable devices, and energy storage systems (ESS) for home or renewable energy generation.
[0261] <Non-aqueous solvent> Non-aqueous electrolytes used in lithium-ion batteries typically contain non-aqueous solvents.
[0262] Various known non-aqueous solvents can be suitably selected as non-aqueous solvents. Preferably, at least one solvent selected from the group consisting of cyclic aprotic solvents and chain-like aprotic solvents is used. When it is desirable to intentionally increase the flash point of the solvent to improve battery safety, a cyclic aprotic solvent is preferred as the non-aqueous solvent.
[0263] (Cyclic aprotic solvent) Examples of cyclic aprotic solvents include, for example, cyclic carbonates, cyclic carboxylic esters, cyclic sulfones, and cyclic ethers.
[0264] One type of cyclic aprotic solvent can be used, or two or more types can be used in combination.
[0265] The content of the cyclic aprotic solvent in the non-aqueous solvent is preferably 10 to 100% by mass, more preferably 20 to 90% by mass, and even more preferably 30 to 80% by mass. By setting such a content, the conductivity of the electrolyte, for example, which is related to the charge and discharge characteristics of the battery, can be improved.
[0266] Examples of cyclic carbonates include ethylene carbonate, propylene carbonate, 1,2-butanediol carbonate, 2,3-butanediol carbonate, 1,2-pentanediol carbonate, and 2,3-pentanediol carbonate. Among these, ethylene carbonate and propylene carbonate, which have high dielectric constants, are preferred. In batteries where graphite is used as the negative electrode active material, ethylene carbonate is more preferred. Two or more cyclic carbonates may also be used in combination.
[0267] Examples of cyclic carboxylic acid esters include, for example, γ-butyrolactone, δ-valerolactone, or alkyl-substituted derivatives such as methyl-γ-butyrolactone, ethyl-γ-butyrolactone, and ethyl-δ-valerolactone.
[0268] Cyclic carboxylic esters have low vapor pressure, low viscosity, and high dielectric constant, which can reduce the viscosity of the electrolyte without lowering its flash point or degree of dissociation. Therefore, cyclic carboxylic esters have the characteristic of improving electrolyte conductivity, an indicator related to the charge-discharge characteristics of the battery, without increasing the flammability of the electrolyte. Thus, when there is an intention to increase the flash point of the solvent, cyclic carboxylic esters are preferred as cyclic aprotic solvents. γ-Butyrolactone is the most preferred.
[0269] Cyclic carboxylic esters are preferably used in combination with other cyclic aprotic solvents and / or chain aprotic solvents. Examples include cyclic carboxylic esters and mixtures (combinations) with cyclic carbonates and / or chain carbonates.
[0270] Examples of combinations of cyclic carboxylic acid esters and cyclic carbonates and / or chain carbonates include: γ-butyrolactone with ethylene carbonate; γ-butyrolactone with ethylene carbonate and dimethyl carbonate; γ-butyrolactone with ethylene carbonate and methyl ethyl carbonate; γ-butyrolactone with ethylene carbonate and diethyl carbonate; γ-butyrolactone with propylene carbonate; γ-butyrolactone with propylene carbonate and dimethyl carbonate; γ-butyrolactone with propylene carbonate... methyl ethyl carbonate; γ-butyrolactone with propylene carbonate and diethyl carbonate; γ-butyrolactone with ethylene carbonate and propylene carbonate; γ-butyrolactone with ethylene carbonate, propylene carbonate, and dimethyl carbonate; γ-butyrolactone with ethylene carbonate, propylene carbonate, and methyl ethyl carbonate; γ-butyrolactone with ethylene carbonate, propylene carbonate, and diethyl carbonate; γ-butyrolactone with ethylene carbonate, dimethyl carbonate, and methyl ethyl carbonate; γ-butyrolactone γ-Butyrolactone with ethylene carbonate, dimethyl carbonate, and diethyl carbonate; γ-Butyrolactone with ethylene carbonate, methyl ethyl carbonate, and diethyl carbonate; γ-Butyrolactone with ethylene carbonate, propylene carbonate, dimethyl carbonate, and methyl ethyl carbonate; γ-Butyrolactone with ethylene carbonate, propylene carbonate, dimethyl carbonate, and diethyl carbonate; γ-Butyrolactone It is associated with ethylene carbonate, propylene carbonate, methyl ethyl carbonate, and diethyl carbonate; γ-butyrolactone with ethylene carbonate, propylene carbonate, dimethyl carbonate, methyl ethyl carbonate, and diethyl carbonate; γ-butyrolactone with sulfolane; γ-butyrolactone with ethylene carbonate and sulfolane; γ-butyrolactone with propylene carbonate and sulfolane; γ-butyrolactone with ethylene carbonate, propylene carbonate, and sulfolane; and γ-butyrolactone with sulfolane and dimethyl carbonate.
[0271] Examples of cyclic sulfones include sulfolane, 2-methylsulfolane, 3-methylsulfolane, dimethyl sulfone, diethyl sulfone, dipropyl sulfone, methyl ethyl sulfone, and methyl propyl sulfone.
[0272] Examples of cyclic ethers include, for instance, dioxane.
[0273] (Chain-like aprotic solvent) Examples of chain-like aprotic solvents include chain carbonates, chain carboxylic esters, chain ethers, and chain phosphates.
[0274] A chain-like aprotic solvent can be used in one form or in combination of two or more.
[0275] The content of the chain-like aprotic solvent in the non-aqueous solvent is preferably 10 to 100% by mass, more preferably 20 to 90% by mass, and even more preferably 30 to 80% by mass.
[0276] Examples of chain carbonates include, for example, dimethyl carbonate, methyl ethyl carbonate, diethyl carbonate, methyl propyl carbonate, methyl isopropyl carbonate, ethyl propyl carbonate, dipropyl carbonate, methyl butyl carbonate, ethyl butyl carbonate, dibutyl carbonate, methyl pentyl carbonate, ethyl pentyl carbonate, dipentyl carbonate, methyl heptacarbonate, ethyl heptacarbonate, diheptyl carbonate, methyl hexyl carbonate, ethyl hexyl carbonate, dihexyl carbonate, methyl octyl carbonate, ethyl octyl carbonate, dioctyl carbonate, and methyl trifluoroethyl carbonate. Two or more chain carbonates may also be used in combination.
[0277] Examples of chain-like carboxylic acid esters include, for instance, methyl tervaline.
[0278] Examples of chain ethers include, for instance, dimethoxyethane.
[0279] Examples of chain phosphate esters include, for instance, trimethyl phosphate.
[0280] (Combination of solvents) The non-aqueous electrolyte may contain only one type of non-aqueous solvent or two or more types.
[0281] One or more cyclic aprotic solvents, one or more chain-like aprotic solvents, or a mixture of cyclic and chain-like aprotic solvents can be used. When there is a particular intention to improve the battery's load characteristics and low-temperature characteristics, it is preferable to use a combination of cyclic and chain-like aprotic solvents as non-aqueous solvents.
[0282] Considering the electrochemical stability of the electrolyte, cyclic carbonates are the preferred choice as cyclic aprotic solvents, while linear carbonates are preferred as linear aprotic solvents. Combinations of cyclic carboxylic esters with cyclic carbonates and / or linear carbonates can also be used to improve the electrolyte conductivity, which is related to the charge-discharge characteristics of the battery.
[0283] Examples of combinations of cyclic and chain carbonates include: ethylene carbonate and dimethyl carbonate; ethylene carbonate and methyl ethyl carbonate; ethylene carbonate and diethyl carbonate; propylene carbonate and dimethyl carbonate; propylene carbonate and methyl ethyl carbonate; propylene carbonate and diethyl carbonate; ethylene carbonate, propylene carbonate and methyl ethyl carbonate; ethylene carbonate, propylene carbonate and diethyl carbonate; ethylene carbonate and dimethyl carbonate, methyl ethyl carbonate; ethylene carbonate and... Dimethyl carbonate, diethyl carbonate; ethylene carbonate and methyl ethyl carbonate, diethyl carbonate; ethylene carbonate and dimethyl carbonate, methyl ethyl carbonate, diethyl carbonate; ethylene carbonate, propylene carbonate and dimethyl carbonate, methyl ethyl carbonate; ethylene carbonate, propylene carbonate and dimethyl carbonate, diethyl carbonate; ethylene carbonate, propylene carbonate and methyl ethyl carbonate, diethyl carbonate; ethylene carbonate, propylene carbonate and dimethyl carbonate, methyl ethyl carbonate, diethyl carbonate.
[0284] The mixing ratio of cyclic carbonates to chain carbonates (cyclic carbonate: chain carbonate), expressed as a mass ratio, is preferably 5:95 to 80:20, more preferably 10:90 to 70:30. By setting such a mixing ratio, the increase in electrolyte viscosity can be suppressed and the degree of electrolyte dissociation can be improved. Therefore, the conductivity of the electrolyte, which is related to the charge-discharge characteristics of the battery, can be improved, and the solubility of the electrolyte can be further improved. Thus, an electrolyte with excellent conductivity at room temperature or low temperature can be produced, thereby improving the battery load characteristics at room temperature to low temperature.
[0285] Lithium-ion batteries contain a non-aqueous electrolyte containing the aforementioned non-aqueous solvent. Therefore, the packaging material constituting the lithium-ion battery (a packaging material for lithium-ion batteries) preferably does not readily leach into the aforementioned non-aqueous solvent, nor does it readily swell due to the aforementioned non-aqueous solvent, and preferably maintains a certain mechanical strength even when exposed to contact with the aforementioned non-aqueous solvent. The aforementioned sealing film and the aforementioned laminate having a layer formed from this composition exhibit excellent resistance to whitening and are not prone to, for example, leaching into the aforementioned non-aqueous solvent, nor swelling due to the aforementioned non-aqueous solvent, and maintain a certain mechanical strength even when exposed to contact with the aforementioned non-aqueous solvent. Therefore, the aforementioned sealing film and the aforementioned laminate can be suitably used as a packaging material for lithium-ion batteries.
[0286] Example The following describes the content of this disclosure in more detail based on embodiments, but the content of this disclosure is not limited to these embodiments in any way.
[0287] The following shows the various polymers used in the examples and comparative examples.
[0288] [1-Butene-propylene-ethylene copolymer (A)] 1-Butene-propylene-ethylene copolymers (A-1) to (A-7) obtained from the manufacturing examples described later were used.
[0289] [Propylene polymer (B)] (B-1); Random polypropylene (manufactured by Prime Polymer Co., Ltd., trade name Prime Polypro F327, MFR (230℃, 2.16kg load): 7g / 10min, melting point: 140℃, crystallization temperature: 97℃, mm: 95.3%) (B-2); Block polypropylene (manufactured by SunAllomer Co., Ltd., trade name SunAllomer PC480A, MFR (230℃, 2.16kg load): 2.0g / 10min, melting point: 165℃, crystallization temperature: 116℃) [Vinyl polymers (C)] (C1-1); Low-density polyethylene produced by high-pressure process (manufactured by DOW-MITSUI POLYCHEMICALS CO., LTD., trade name MIRASON 11P, MFR (190℃, 2.16kg load): 7.2g / 10min, density: 0.917g / cm³). 3 ) (C2-1); Ethylene-propylene copolymer (MFR (190℃, 2.16kg load): 0.6g / 10min, density: 0.869g / cm³) 3 ) [Other ingredients] (PER); Propylene-ethylene copolymer (commercially available, ethylene content 12.5 mol%, propylene content 87.5 mol%, MFR (230℃, 2.16 kg load): 8 g / 10 min, melting point 80℃) [Preparation of 1-Butene-Propylene-Ethylene Copolymer (A)] [Example 1] Hexane is supplied at a rate of 14.2 L / h to one feed port of a 300 L continuous polymerizer. From other feed ports, a mixed hexane solution of isopropylidene (3-tert-butyl-5-methylcyclopentadienyl-fluorenyl) zirconium dichloride (the main catalyst), modified methylaluminoxane, and triisobutylaluminum is continuously supplied at a rate of 0.22 L / h (total hexane flow rate 10 L / h). The zirconium equivalent concentration of the main catalyst in the above mixed solution is 0.5 mmol / L, the aluminum equivalent concentration of the modified methylaluminoxane is 4 mmol / L, and the aluminum equivalent concentration of the triisobutylaluminum is 100 mmol / L. Simultaneously, 1-butene, propylene, ethylene, and hydrogen are continuously supplied from another feed port of the polymerizer at a rate of 23.5 kg / h, 1.3 kg / h, 0.4 kg / h, and 4.4 NL / h. Continuous solution polymerization is carried out under the conditions of polymerization temperature of 60°C, polymerization pressure of 0.79 MPaG, and residence time of 1.5 hours to obtain 1-butene·propylene·ethylene copolymer (A-1).
[0290] [Examples 2-7] As shown in Table 1, the supply of 1-butene, propylene, ethylene and hydrogen, as well as the polymerization pressure, were adjusted. Otherwise, the same method as in Example 1 was used to produce 1-butene-propylene-ethylene copolymers (A-2) to (A-7).
[0291] [Properties of 1-Butene·propylene·ethylene copolymer and propylene·ethylene copolymer] The physical properties of the 1-butene-propylene-ethylene copolymer (A) of Examples 1-7 and the physical properties of the propylene-ethylene copolymer (PER) of Comparative Example 1 were determined by the following methods. The results are shown in Table 1.
[0292] <1-Butene content, propylene content, and ethylene content> For the 1-butene, propylene, and ethylene contents in 1-butene-propylene-ethylene copolymer (A) and propylene-ethylene copolymer (PER), the following conditions are applied. 13 C-NMR measurements were performed using the obtained... 13 The content of structural units derived from 1-butene is calculated by C-NMR spectroscopy analysis. In this specification, the content of structural units derived from 1-butene is referred to as "1-butene content", the content of structural units derived from propylene is referred to as "propylene content", and the content of structural units derived from ethylene is referred to as "ethylene content".
[0293] Apparatus: Bruker BioSpin AVANCE cryo-500 MRI scanner Observation kernel: 13 C (125MHz) Solvent: o-dichlorobenzene / deuterated benzene mixed solvent (capacity ratio: 80 / 20) Sample concentration: 20 mg / 0.6 mL Measurement temperature: 120℃ Sequence: Single-pulse proton broadband decoupling Pulse width: 4.7 μs (45° pulse) Repeat time: 5.5 seconds Total number of times: 128 Chemical shift reference value: Carbon signal of the methylene group in the butene side chain: 27.50 ppm Melt Flow Rate (MFR) According to ASTM D1238, the MFR was determined at 190°C and 2.16 kg load and at 230°C and 2.16 kg load.
[0294] <Isosteretic five-unit composition ratio (mmmm)> For the isotactic regularity (mmmm) of the five-unit group of 1-butene·propylene·ethylene copolymer (A) and propylene·ethylene copolymer (PER), in the above 13 In the C-NMR spectrum, with the chemical shift of the peak at the quintuple group denoted by mmmm set to 27.5 ppm, the peak area S at 27.5 ppm and the total area S' of peaks appearing in the range of 27.3 ppm to 26.3 ppm are calculated using the following formula. (Detection limit: set to 0.01%.) (mmmm)=S / (S+S')×100(%) Here, the main peaks appearing in the range of 27.3 ppm to 26.3 ppm are those attributed to mmmr (27.3 ppm), mmrr and rmmr (27.2 ppm), and mrrm (26.3 ppm).
[0295] For the isotactic regularity (mmmm) of the pentamelist of propylene polymer (B), with a chemical shift of 21.8 ppm for the peak at the peak of the pentamelist represented by mmmm, the peak area S at 21.8 ppm and the total area S' of peaks appearing in the range of 21.6 ppm to 19.8 ppm are calculated using the following formula. (Detection limit: set to 0.01%) (mmmm)=S / (S+S')×100(%) Here, the main peaks appearing in the range of 21.6 ppm to 19.8 ppm are those attributed to mmmr (21.6 ppm), mmrr (21.0 ppm), rrmr and mmrm (20.8 ppm).
[0296] If mmmm cannot be calculated, it is represented as "na"; if mmmm has not been measured, it is represented as "nd".
[0297] Intrinsic viscosity [η] For the intrinsic viscosity [η] of 1-butene-propylene-ethylene copolymer (A) and propylene-ethylene copolymer (PER), the measurement was performed at 135°C using an Ubbelohde viscometer in a decahydronaphthalene solvent. Approximately 20 mg of resin was dissolved in 15 mL of decahydronaphthalene, and the specific viscosity ηsp was measured in an oil bath heated to 135°C. The solution was diluted by adding 5 mL of decahydronaphthalene solvent, and the specific viscosity ηsp was measured again. This dilution was repeated twice more, and the value of ηsp / C, extrapolated to zero from the concentration (C), was calculated as the intrinsic viscosity [η].
[0298] [η]=lim (ηsp / C) (C→0) <Weight-average molecular weight (Mw), number-average molecular weight (Mn), and molecular weight distribution (Mw / Mn)> As a GPC apparatus, a Waters Alliance GPC-2000 gel permeation chromatograph was used to determine Mw and Mn converted to polystyrene under the following conditions, and to calculate Mw / Mn.
[0299] Separation columns: 2 TSKgel GNH6-HT columns and 2 TSKgel GNH6-HTL columns manufactured by Tosoh Corporation (both columns are 7.5 mm in diameter and 300 mm in length). Column temperature: 140℃ Mobile phase: o-dichlorobenzene (manufactured by FUJIFILM Wako Pure Chemical Corporation) containing 0.025% by weight of BHT (manufactured by Takeda Pharmaceutical Co., Ltd.) as an antioxidant. Motion rate: 1.0 mL / min Sample concentration: 15 mg / 10 mL Sample injection volume: 400 μL Detector: Differential refractometer Standard polystyrene: For molecular weights Mw < 1000 and Mw > 4 × 10⁻⁶ 6 In the case of using Tosoh Corporation, with a molecular weight of 1000≤Mw≤4×10 6 In such cases, it is manufactured using Pressure Chemical Co.
[0300] Melting point (Tm), enthalpy of fusion, and glass transition temperature (Tg) In the calorimetry determination using a differential scanning calorimeter (DSC) as described in this disclosure, approximately 6-10 mg of sample is accurately weighed, sealed in an aluminum dish, and cooled from room temperature to -70°C at a cooling rate of 20°C / min (first cooling), held at this temperature for 5 minutes. The temperature is then increased from -70°C to 200°C at a heating rate of 20°C / min (first heating), and measured using DSC. After holding at 200°C for 10 minutes, the temperature is then decreased to -70°C at a cooling rate of 20°C / min (second cooling), and measured using DSC. After holding at -70°C for 1 minute, the temperature is again increased from -70°C to 200°C at a heating rate of 20°C / min (second heating), and measured using DSC.
[0301] It should be noted that the melting point of 1-butene·propylene·ethylene copolymer (A) measured in the first heating in the heat measurement using differential scanning calorimeter (DSC) is set as "melting point (1st)" and the enthalpy of fusion is set as "enthalpy of fusion (1st)". The melting point measured in the second heating is set as "melting point (2nd)" and the enthalpy of fusion is set as "enthalpy of fusion (2nd)".
[0302] The enthalpy of fusion is calculated from the cumulative value of the crystalline melting peaks during heating. The melting point (Tm) is the temperature of the peak of the crystalline melting peak during heating. The glass transition temperature (Tg) is the temperature at which the baseline shift occurs during the second heating. If more than two melting peaks are observed, the lowest temperature among the peak temperatures is taken as the melting point. No observed melting peak refers to no observed crystalline melting peak with an enthalpy of fusion greater than 1 J / g. When neither the enthalpy of fusion nor the melting point (Tm) is observed, it is indicated as "na".
[0303] <Mechanical properties (23℃)> The pressurized sheet prepared under the following conditions is stored at room temperature for more than 10 days, and the resulting material (hereinafter also referred to as "test sheet for mechanical properties") is used for testing.
[0304] Compressor: Manufactured by KANSAI ROLL Co., Ltd. (Model: PEWE-70 / 50 35) Preheating time: 4 minutes Preheating and pressurization temperature: 190℃ Pressure: 10MPa Pressurization time: 3 min Cooling rate: 40℃ / min (using another pressurizer set to 20℃, pressurize at 10MPa for 4 minutes to cool to room temperature) For the test pieces used for the above mechanical properties, the yield stress, breaking strength (TS), elongation at break (between chucks, EL), and Young's modulus (YM) were determined according to ASTM D638 and No. 4 dumbbell (measurement temperature 23℃, tensile speed = 50mm / min).
[0305] <Shore A hardness (instantaneous value) and Shore D hardness (maximum value)> For 1-butene-propylene-ethylene copolymer (A) or propylene-ethylene copolymer (PER), a 100 μm thick release PET film (manufactured by Toray, trade name Lumirror) was used as the release film. A hydraulic thermoforming machine set to 190°C was used. After heating for 4 minutes, it was formed under a pressure of 10 MPa for 3 minutes, and then cooled for 4 minutes under a pressure of 10 MPa at 20°C to produce a 2 mm thick sheet (test sheet).
[0306] After being pressurized and stored at room temperature for more than 10 days, the Shore A hardness and Shore D hardness are measured.
[0307] Using a Durometer (Type A tester), read the scale immediately after the indenter contacts the test piece, which is taken as the Shore A hardness (according to ASTM D2240).
[0308] Using a Durometer (D-type tester), after the indenter contacts the test piece, read the maximum value on the scale as the Shore D hardness (according to ASTM D2240). If the Shore D hardness has not been measured, it is represented as "nd".
[0309] [Table 1] [Examples A1-A14, Comparative Examples a1-a6] Using a Labo Plastomill (manufactured by Toyo Seiki Co., Ltd.), the polymer was mixed for 5 minutes at 200°C and 40 rpm in the proportions (mass%) listed in Table 2-1 to obtain a polymer composition. For the obtained composition or the propylene-based polymer (B), a hydraulic hot press set to 190°C was used. After heating for 4 minutes, molding was performed under a pressure of 10 MPa for 3 minutes, followed by cooling at 20°C and 10 MPa for 4 minutes, thereby producing a 2 mm thick sheet (test sheet).
[0310] <Mechanical properties (23℃)> Instead of the 1-butene-propylene-ethylene copolymer, the polymer composition obtained in the examples or comparative examples was used, and the tensile strength (TS), elongation at break (between chucks, EL), and Young's modulus (YM) were measured in the same manner as described above for <Mechanical Properties (23°C)>. The results are shown in Table 2-1.
[0311] <Heat resistance (mechanical properties (80℃))> For the polymer composition obtained in the examples or comparative examples, a sheet (test sheet) with a thickness of 2 mm was produced by heating it for 5 minutes using a hydraulic hot press set to 190°C, molding it under a pressure of 7.5 MPa for 2 minutes, and then cooling it under a pressure of 7.5 MPa at 20°C for 5 minutes.
[0312] After being left at room temperature for more than 7 days from the start of molding, 5A-shaped dumbbells were manufactured from the above-mentioned sheet material in accordance with JIS K7161-2. For these dumbbells, the tensile strength (TS), elongation at break (between chucks, EL), and Young's modulus (YM) were measured at 80°C and a tensile speed of 500 mm / min. The obtained values were used as indicators of heat resistance.
[0313] <Whitening resistance> For the polymer composition obtained in the examples or comparative examples, a sheet (test sheet) with a thickness of 0.5 mm was produced by heating it for 5 minutes using a hydraulic hot press set to 190°C, molding it under a pressure of 7.5 MPa for 2 minutes, and then cooling it for 5 minutes under a pressure of 7.5 MPa at 20°C.
[0314] After being left at room temperature for more than 7 days from the time of molding, dumbbells of shape 2 as specified in JIS K6251 were made from the above-mentioned sheet. For this dumbbell, the hue before elongation (L value (before elongation)) and the hue after elongation by 15 mm at 23°C and a stretching speed of 50 mm / min were measured using a spectrophotometer (KONICA MINOLTA Co., Ltd., CM-3700d) were determined. The hue change (ΔL) was calculated based on the following formula. The smaller the ΔL value, the better the whitening resistance of the above polymer composition.
[0315] ΔL = L value (after elongation) - L value (before elongation) [Table 2-1] Compared to the polymer compositions of Comparative Examples a1-a6 or propylene-based polymers, the polymer compositions (X) of Examples A1-A14 exhibit high breaking stress or low tensile modulus, and demonstrate excellent balance between flexibility and tensile strength. For example, when comparing Example A10 with Comparative Example a1 at the same breaking stress, the Example A10 shows a lower tensile modulus and superior flexibility compared to the Comparative Example. Furthermore, when comparing Example A9 with the same tensile modulus and Comparative Example a1, the Example A9 shows a higher breaking stress and superior strength compared to the Comparative Example.
[0316] Furthermore, compared to the polymer compositions of Comparative Examples a1-a6 or propylene-based polymers, the TS*log of the polymer compositions (X) of Examples A1-A14 is significantly higher. 10 The high value of (YM) / ΔL results in an excellent balance of softness, tensile strength and whitening resistance in both room temperature (23°C) and high temperature (80°C) environments.
[0317] [Examples A15, A16, Comparative Examples a3, a7] Using a Labo Plastomill (manufactured by Toyo Seiki Co., Ltd.), the polymer was mixed for 5 minutes at 200°C and 40 rpm in the proportions (mass%) listed in Table 2-2 to obtain a polymer composition. For the obtained composition or the propylene-based polymer (B), a hydraulic hot press set to 190°C was used. After heating for 4 minutes, molding was performed under a pressure of 10 MPa for 3 minutes, followed by cooling at 20°C and 10 MPa for 4 minutes, thereby producing a 2 mm thick sheet (test sheet).
[0318] <Mechanical properties (23℃)> Instead of the 1-butene-propylene-ethylene copolymer, the polymer composition or propylene-based polymer (B) obtained in the examples or comparative examples was used. Otherwise, the same procedure was followed as described above for <Mechanical Properties (23°C)> to determine the breaking strength (TS), elongation at break (between chucks, EL), and Young's modulus (YM). The results are shown in Table 2-2.
[0319] <Shore D Hardness (Maximum)> Instead of the 1-butene-propylene-ethylene copolymer, the polymer composition or propylene-based polymer (B) obtained in the examples or comparative examples was used. Otherwise, the Shore D hardness (maximum value) was measured in the same manner as the <Shore A hardness (instantaneous value) and Shore D hardness (maximum value)> above.
[0320] Haze (transparency) and total light transmittance According to JIS K7136:2000, using a 2mm thick sheet obtained by pressure molding, the haze and total light transmittance were measured using a haze meter "HM-150" manufactured by Murakami Color Technology Research Institute Co., Ltd.
[0321] [Table 2-2] Compared to the polymer composition of Comparative Example a7, the polymer compositions (X) of Examples A15 and A16 exhibit high breaking stress or low tensile modulus, and demonstrate excellent balance between softness and tensile strength. For example, when comparing Example A16 with Comparative Example a7 at the same level of breaking stress, the Example A16 has a lower tensile modulus and superior softness compared to the Comparative Example, and also exhibits lower haze, higher total light transmittance, and superior transparency. Furthermore, when comparing Example A15 with Comparative Example a7 at the same level of tensile modulus, the Example A15 has a higher breaking stress and superior strength compared to the Comparative Example, and also exhibits lower haze, higher total light transmittance, and superior transparency.
[0322] [Examples B1, B2, and Comparative Examples b1-b3] Using the 1-butene·propylene·ethylene copolymers (A-6) and (A-7) obtained in Examples 6 and 7, an extruder was used ( The raw materials listed in Table 2-3 (40 mm) were mixed in the proportions (mass%) shown in Table 2-3. The resulting granules were extruded at 230°C using a casting film forming machine to produce a 50 μm thick single-layer unstretched film. The obtained single-layer unstretched film was evaluated as follows. The results are shown in Table 2-3.
[0323] <Mechanical properties (23℃)> For the above-mentioned unstretched film, in accordance with JIS K7127:1999, the tensile strength (TS), elongation at break (between chucks, EL), and Young's modulus (YM) in the longitudinal direction were measured using a short grid with a width of 15 mm (measurement temperature 23℃, stretching speed = 200 mm / min).
[0324] <Membrane Shock> The impact strength at 0°C was determined using a membrane impact tester (with a 1-inch tip diameter and a 3J hammer) manufactured by Toyo Seiki Co., Ltd.
[0325] <Tear Test> The tear strength in the MD (longitudinal) and TD (transverse) directions was measured at 0°C using a digital Elmendorf tearing tester (MD direction: 4N, TD direction: 16N) manufactured by Toyo Seiki Co., Ltd.
[0326] [Table 2-3] Compared to the polymer compositions of the comparative examples, the polymer compositions (X) of Examples B1 and B2 exhibit high breaking stress or low tensile modulus, and demonstrate excellent balance between softness and strength. For example, when comparing Example B1 with Comparative Example B1 at the same breaking stress, the Example B1 shows a lower tensile modulus and superior softness, as well as superior impact resistance and tear resistance compared to the Comparative Example. Furthermore, when comparing Example B2 containing an ethylene-based polymer (C) with Comparative Example B2 at the same breaking stress, the Example B2 shows a lower tensile modulus, superior softness, and superior impact resistance and tear resistance compared to the Comparative Example.
Claims
1. 1-Butene-propylene-ethylene copolymer (A), which satisfies the following requirements (A1) and (A2): (A1) The content of the structural unit (i) derived from 1-butene is 50~96 mol%. The content of propylene-derived structural unit (ii) is 1-40 mol%. And, the content of the ethylene-derived structural unit (iii) is 3~20 mol% (wherein, The total of structural unit (i), structural unit (ii) and structural unit (iii) is set to 100 mol%. (A2) The ratio of weight-average molecular weight (Mw) to number-average molecular weight (Mn) (Mw / Mn) determined by gel permeation chromatography (GPC) and converted to polystyrene is less than 3.
0.
2. The 1-butene-propylene-ethylene copolymer (A) as described in claim 1, wherein it satisfies at least one of the following requirements (A3) and (A4): (A3) The melt flow rate (MFR) measured according to ASTM D1238 at 230°C and 2.16 kg load is 1~100 g / 10 min; (A4) The molar ratio (1-butene / ethylene) of the content of structural unit (i) derived from 1-butene to the content of structural unit (iii) derived from ethylene is 6 or more.
3. The 1-butene-propylene-ethylene copolymer (A) as described in claim 1 or 2, wherein, The molar ratio (1-butene / ethylene) of the required element (A4) is 9.1 or higher.
4. The 1-butene-propylene-ethylene copolymer (A) as described in claim 1 or 2, wherein it satisfies the following requirement (A8): (A8) The melting point (Tm) measured during the first heating of the differential scanning calorimeter (DSC) was observed below 60°C, and the measured enthalpy of fusion was 2~50 J / g. No melting peak was observed during the second heating.
5. The 1-butene-propylene-ethylene copolymer (A) as described in claim 1 or 2, wherein it satisfies the following requirement (A5): (A5) Through 13 The isotactic five-unit composition (mmmm) calculated by C-NMR is over 90%.
6. A polymer composition (X) comprising: The 1-butene-propylene-ethylene copolymer (A) according to claim 1, and A propylene polymer (B) that meets the following requirements (B1) and (B2). (B1) The melting point (Tm) measured during the first heating of the differential scanning calorimeter (DSC) is 100~170℃; (B2) Through 13 The isotactic five-unit composition (mmmm) calculated by C-NMR is over 80%.
7. The polymer composition (X) of claim 6, wherein, The propylene polymer (B) is atactic polypropylene or block polypropylene.
8. The polymer composition (X) as claimed in claim 6 or 7, wherein the following requirements (X1-2) are satisfied: The content of (X1-2)1-butene·propylene·ethylene copolymer (A) is 1~36% by mass, and the content of propylene polymer (B) is 64~99% by mass (wherein, The total of copolymer (A) and propylene polymer (B) is set at 100% by mass.
9. The polymer composition (X) of claim 6, further comprising an ethylene polymer (C).
10. The polymer composition (X) according to claim 9, wherein, The propylene polymer (B) is atactic polypropylene or block polypropylene.
11. The polymer composition (X) according to claim 9 or 10, wherein, The ethylene-based polymer (C) is a high-pressure low-density polyethylene that meets the following requirement (C1) or an ethylene-α-olefin copolymer that meets the following requirement (C2): (C1) The density of high-pressure low-density polyethylene, measured according to ASTM D1505, is 900~925 kg / m³. 3 , (C2) Through 13 The ethylene-α-olefin copolymer, as determined by C-NMR, has at least ethylene-derived structural units and α-olefin-derived structural units with 3 to 20 carbon atoms, wherein the content of the ethylene-derived structural units is 60 to 99 mol%, and the content of the α-olefin-derived structural units with 3 to 20 carbon atoms is 1 to 40 mol%.
12. The polymer composition (X) according to claim 9 or 10, wherein it satisfies the following requirements (X1-3): The content of (X1-3) 1-butene·propylene·ethylene copolymer (A) is 8~35% by mass, the content of propylene polymer (B) is 48~88% by mass, and the content of ethylene polymer (C) is 4~17% by mass (of which, The total content of the copolymer (A), the polymer (B), and the polymer (C) is set to 100% by mass.
13. The polymer composition (X) as claimed in claim 6 or 7, wherein it satisfies the following requirement (X1-1): The content of (X1-1) 1-butene-propylene-ethylene copolymer (A) is higher than 36% by mass and lower than 99% by mass, and the content of propylene polymer (B) is higher than 1% by mass and lower than 64% by mass (wherein, The total of 1-butene-propylene-ethylene copolymer (A) and propylene polymer (B) is set at 100% by mass.
14. A molded article comprising the 1-butene-propylene-ethylene copolymer (A) according to claim 1 or 2, or the polymer composition (X) according to any one of claims 6-7, 9-10.
15. The molded article as described in claim 14, wherein it is a film.
16. A laminate comprising the molded body of claim 14.
17. An energy storage device comprising the molded body as described in claim 14.
Citation Information
Patent Citations
Catalysts, these catalysts and production of these catalyst polymerization process
JP1989501950A
Production method for ethylene copolymer
JP2004051676A
Butene-1 (co)polymer with low isotacticity
JP2008517130A
Highly flowable 1-butene polymer and process for producing the same
WO2003070788A1